Image forming device and process cartridge

By using the core-shell structure toner particles of the binder resin with specific structures and monoester compound wax in electrophotography equipment, the pollution and low-temperature fixability problems of photosensitive members in high-temperature and high-humidity environments are solved, and the image quality is achieved Stability and durability are improved.

CN112882360BActive Publication Date: 2024-12-24CANON KK
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202011357592.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-11-29
Filing Date
2020-11-27
Publication Date
2024-12-24
Estimated Expiration
2040-11-27

AI Technical Summary

Technical Problem

When existing electrophotographic equipment is used in high temperature and high humidity environments, contamination of the photosensitive member causes image quality to deteriorate, and low temperature fixing and environmental stability are difficult to achieve at the same time.

Method used

The core-shell structure toner particles of the binder resin and monoester compound wax with a specific structure are used to improve the durability of the photosensitive member by combining it with the core-shell structure of the toner particles and the composition of the wax. and low temperature fixability.

Benefits of technology

Maintain image quality in high temperature and high humidity environments, prevent wax from adhering to the photosensitive member, improve the durability and low temperature fixability of the photosensitive member, and ensure image clarity and storage stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112882360B_ABST
    Figure CN112882360B_ABST
Patent Text Reader

Abstract

The present invention relates to an image forming apparatus and a processing box. An image forming apparatus comprising an electrophotographic photosensitive member and a developing device for supplying a toner onto the electrophotographic photosensitive member, the developing device having a toner, wherein the electrophotographic photosensitive member has a surface layer containing a binder resin (A), the toner having toner particles, the toner particles having a core containing a binder resin (B) and a wax and a shell layer formed on the surface of the core, the binder resin (A) having a predetermined structure, and the wax containing a predetermined monoester compound; and a processing box.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an image forming apparatus and a process cartridge. Background Art

[0002] Image forming apparatuses utilizing electrophotography (electrophotographic apparatuses) are required to have environmental stability, long life, energy saving, and miniaturization, and in order to meet these requirements, further improvements in various properties of toners and electrophotographic photosensitive members (hereinafter, also simply referred to as "photosensitive members") are also required.

[0003] In particular, in image forming apparatuses (electrophotographic apparatuses), it is important to stably provide high-quality images regardless of various use environments and the time of use. In harsh environments such as continuous use under high temperature and high humidity environments, photosensitive members may be affected, so it is desirable that the environmental stability and durability thereof are high. At the same time, from the viewpoint of high speed and energy saving, the toner needs to have further improved low-temperature fixing performance.

[0004] In order to solve these problems, generally, a charge generating substance and a charge transporting substance are bonded to a binder resin of a photosensitive member, and the durability of the photosensitive member can be improved by hardening the binder resin. Japanese Patent Application Publication No. 2015-169800 proposes a photosensitive member in which durability and oil crack resistance are improved by improving a binder resin.

[0005] Regarding low temperature fixability, it is important to first create a state in which fusing is easier when the binder resin of the toner is plasticized during fixing. In particular, there are various means for improving low temperature fixability, and generally, low temperature fixability can be improved by using a toner having a binder resin designed to be easily plasticized.

[0006] However, with this method, the resin is soft even when not fixed, and problems with environmental stability, especially storage stability under high temperature environments, are apparent. Japanese Patent Application Publication No. 2018-13589 proposes a toner having improved low-temperature fixability by adding a crystalline material to the toner. In addition, WO 2014 / 157424 proposes a toner having improved heat offset resistance and low-temperature fixability by using a predetermined monoester compound.

[0007] In addition, for miniaturization, it is effective to reduce the number of components. For example, according to Japanese Patent Application Publication No. 2017-97161, miniaturization is achieved by eliminating a cleaning blade. Summary of the invention

[0008] As a result of the study, the present inventors have found that when the method described in Japanese Patent Application Publication No. 2015-169800 is used continuously for a long time under a high temperature and high humidity environment, there is a concern that the image quality may deteriorate due to contamination of the photosensitive member. When a crystalline material such as that described in Japanese Patent Application Publication No. 2018-13589 is used as a plasticizer, such deterioration of image quality is particularly likely to occur. Therefore, there are still problems in obtaining low temperature fixability and high image quality under a high temperature and high humidity environment for a long time.

[0009] Furthermore, the toner described in WO 2014 / 157424 has a problem that image quality degradation caused by a photosensitive member may occur when used continuously for a long period of time under a high-temperature and high-humidity environment.

[0010] In addition, in the image forming apparatus disclosed in Japanese Patent Application Publication No. 2017-97161, the physical properties required of the colorant and the photosensitive member are further improved, but in the embodiments of Japanese Patent Application Publication No. 2015-169800, Japanese Patent Application Publication No. 2018-13589, and WO 2014 / 157424, as described in Japanese Patent Application Publication No. 2017-97161, when the cleaning scraper or the paper powder recovery mechanism is removed, the durability problem becomes more significant.

[0011] The present disclosure provides an image forming apparatus and a process cartridge that simultaneously achieves low-temperature fixability and environmental stability.

[0012] The present inventors have found that the above problems can be solved by using a photosensitive member using a binder resin having a specific structure and a toner having toner particles having a core-shell structure and including a wax containing a monoester compound having a specific structure.

[0013] That is, the image forming apparatus of the present disclosure is an image forming apparatus including:

[0014] an electrophotographic photosensitive member; and

[0015] A developing device for supplying toner to an electrophotographic photosensitive member, the developing device having toner, wherein

[0016] The electrophotographic photosensitive member has a surface layer containing a binder resin (A),

[0017] The toner has toner particles,

[0018] The toner particles have a core-shell structure having:

[0019] a core comprising a binder resin (B) and a wax; and

[0020] A shell is formed on the surface of the core,

[0021] The binder resin (A) has:

[0022] A structure represented by the following formula (1); and

[0023] The structure represented by the following formula (2):

[0024]

[0025] Among them, R 11 and R 21 Each independently represents a hydrogen atom or a methyl group. 22 and R 23 Each independently represents a hydrogen atom, a methyl group, an ethyl group or a phenyl group, or R 22 and R 23 are connected to each other to form a cycloalkylidene group,

[0026] The wax contains a monoester compound represented by the following formula (3):

[0027] R 31 -COO-R 32 (3)

[0028] Among them, R 31 and R 32 Each independently represents an alkyl group having 10 to 30 carbon atoms.

[0029] In addition, the process cartridge of the present disclosure is a process cartridge that is detachably mounted to the main body of the image forming apparatus,

[0030] Processing box includes:

[0031] an electrophotographic photosensitive member; and

[0032] A developing device for supplying toner to an electrophotographic photosensitive member, the developing device having toner, wherein

[0033] The electrophotographic photosensitive member has a surface layer containing a binder resin (A),

[0034] The toner has toner particles;

[0035] The toner particles have a core-shell structure having:

[0036] a core comprising a binder resin (B) and a wax; and

[0037] A shell is formed on the surface of the core,

[0038] The binder resin (A) has:

[0039] A structure represented by the following formula (1); and

[0040] The structure represented by the following formula (2):

[0041]

[0042] Among them, R 11 and R 21 Each independently represents a hydrogen atom or a methyl group. 22 and R 23 Each independently represents a hydrogen atom, a methyl group, an ethyl group or a phenyl group, or R 22 and R 23 are connected to each other to form a cycloalkylidene group, and

[0043] The wax contains a monoester compound represented by the following formula (3):

[0044] R 31 -COO-R 32 (3)

[0045] Among them, R 31 and R 32 Each independently represents an alkyl group having 10 to 30 carbon atoms.

[0046] According to the present disclosure, an image forming apparatus and a process cartridge which simultaneously achieve low-temperature fixability and environmental stability can be provided.

[0047] Further features of the present invention will become apparent from the following description of exemplary embodiments with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 is a schematic diagram of an example of an image forming apparatus. DETAILED DESCRIPTION

[0049] In the present disclosure, unless otherwise specified, the expression "from XX to YY" or "XX to YY" expressing a numerical range means a numerical range including the lower limit and the upper limit as endpoints.

[0050] As referred to herein, a monomer unit means a reaction form of a monomer substance in a polymer. For example, a segment of carbon-carbon bonds in a main chain obtained by polymerizing a vinyl monomer in a polymer is considered to be a unit.

[0051] As referred to herein, a crystalline resin or a crystalline material means a resin or a material showing a clear endothermic peak in differential scanning calorimetry.

[0052] Hereinafter, embodiments of the present disclosure will be described in more detail, but the present invention is not limited thereto.

[0053] The present inventors have found that the above problems can be solved by using a photosensitive member using a binder resin having a specific structure and a toner having toner particles having a core-shell structure and including a wax containing a monoester compound having a specific structure.

[0054] That is, the image forming apparatus of the present disclosure is an image forming apparatus including:

[0055] an electrophotographic photosensitive member; and

[0056] A developing device for supplying toner to an electrophotographic photosensitive member, the developing device having toner, wherein

[0057] The electrophotographic photosensitive member has a surface layer containing a binder resin (A),

[0058] The toner has toner particles,

[0059] The toner particles have a core-shell structure having:

[0060] a core comprising a binder resin (B) and a wax; and

[0061] A shell is formed on the surface of the core,

[0062] The binder resin (A) has:

[0063] A structure represented by the following formula (1); and

[0064] The structure represented by the following formula (2):

[0065]

[0066] Among them, R 11 and R 21 Each independently represents a hydrogen atom or a methyl group. 22 and R 23 Each independently represents a hydrogen atom, a methyl group, an ethyl group or a phenyl group, or R 22 and R 23 are connected to each other to form a cycloalkylidene group,

[0067] The wax contains a monoester compound represented by the following formula (3):

[0068] R 31 -COO-R 32 (3)

[0069] Among them, R 31 and R 32 Each independently represents an alkyl group having 10 to 30 carbon atoms.

[0070] In addition, the process cartridge of the present disclosure is a process cartridge that is detachably mounted to the main body of the image forming apparatus,

[0071] Processing box includes:

[0072] an electrophotographic photosensitive member; and

[0073] A developing device for supplying toner to an electrophotographic photosensitive member, the developing device having toner, wherein

[0074] The electrophotographic photosensitive member has a surface layer containing a binder resin (A),

[0075] The toner has toner particles;

[0076] The toner particles have a core-shell structure having:

[0077] a core comprising a binder resin (B) and a wax; and

[0078] A shell is formed on the surface of the core,

[0079] The binder resin (A) has:

[0080] A structure represented by the following formula (1); and

[0081] The structure represented by the following formula (2):

[0082]

[0083]

[0084] Among them, R 11 and R 21 Each independently represents a hydrogen atom or a methyl group. 22 and R 23 Each independently represents a hydrogen atom, a methyl group, an ethyl group or a phenyl group, or R 22 and R 23 are connected to each other to form a cycloalkylidene group, and

[0085] The wax contains a monoester compound represented by the following formula (3):

[0086] R 31 -COO-R 32 (3)

[0087] Among them, R 31 and R 32 Each independently represents an alkyl group having 10 to 30 carbon atoms.

[0088] By using a toner having toner particles having a core-shell structure and including a wax containing a monoester compound represented by formula (3) in combination with a photosensitive member having an outer surface containing a binder resin (A) having a structure represented by formula (1) and a structure represented by formula (2), the affinity between the photosensitive member and the wax can be appropriately maintained. The affinity is the compatibility between the wax and the photosensitive member, and exerts an effect on the adsorption and releasability of the toner.

[0089] Since the affinity between the photosensitive member and the wax is not too high, even when the wax oozes out to the surface of the toner particles under a high temperature and high humidity environment, the wax can be prevented from being attached to the photosensitive member. In addition, since the affinity is not too low, the sharpness of the image can be prevented from being reduced due to the rolling of the toner during transfer.

[0090] Here, the “surface layer” is a layer located on the outermost surface side of the photosensitive member, and the outer surface of the surface layer is in contact with the toner.

[0091] The binder resin (A) has a structure represented by the following formula (1) and a structure represented by the following formula (2).

[0092]

[0093] Among them, R 11 and R 21 Each independently represents a hydrogen atom or a methyl group. 22 and R 23 Each independently represents a hydrogen atom, a methyl group, an ethyl group or a phenyl group, or R 22 and R 23 are connected to each other to form a cycloalkylidene group.

[0094] The carbon number of the cycloalkylidene group is not particularly limited, but is preferably 4 to 12, and more preferably 5 to 8.

[0095] By including the binder resin (A) having the structure represented by formula (1) and the structure represented by formula (2) in the surface layer of the photosensitive member, wear of the photosensitive member due to friction is suppressed, and electrical characteristics can be maintained while improving durability.

[0096] When the binder resin (A) does not have the structure represented by formula (1), durability is impaired and image quality deteriorates during continuous use. In addition, when the binder resin (A) does not have the structure represented by formula (2), degradation of electrical properties leads to degradation of image quality.

[0097] From the viewpoint of durability and electrical properties, the molar ratio of the structure represented by formula (1) to the structure represented by formula (2) in the binder resin (A) [(structure represented by formula (1)):(structure represented by formula (2))] is preferably 25 / 75 to 70 / 30, and more preferably 25 / 75 to 50 / 50.

[0098] The weight average molecular weight (Mw) of the binder resin (A) is preferably 10,000 to 300,000, and more preferably 20,000 to 200,000. Mw can be controlled by polymerization conditions such as a blending ratio of monomers and a reaction temperature.

[0099] The binder resin (A) may be a random copolymer in which the structure represented by the formula (1) and the structure represented by the formula (2) are randomly copolymerized. In addition, the binder resin (A) may be an alternating copolymer in which the structure represented by the formula (1) and the structure represented by the formula (2) are alternately copolymerized. In addition, the binder resin (A) may be a periodic copolymer in which at least one structure represented by the formula (1) and at least one structure represented by the formula (2) are periodically copolymerized. In addition, the binder resin (A) may be a block copolymer in which a block having at least one structure represented by the formula (1) and a block having at least one structure represented by the formula (2) are copolymerized.

[0100] There is no particular limitation on the method for producing the binder resin (A) as long as a resin having a structure represented by formula (1) and a structure represented by formula (2) can be produced. Examples of the production method include a method of interfacial polycondensation of a diol compound for forming a structure represented by formula (1), a diol compound for forming a structure represented by formula (2), and phosgene, and a method of transesterifying a diol compound and diphenyl carbonate.

[0101] A more specific example is a method of interfacial polycondensation of a mixture obtained by mixing a diol compound represented by the following formula (1') and a diol compound represented by the following formula (2') with phosgene.

[0102]

[0103] Among them, R 11 and R 21 Each independently represents a hydrogen atom or a methyl group. 22 and R 23 Each independently represents a hydrogen atom, a methyl group, an ethyl group or a phenyl group, or R 22 and R 23 are connected to each other to form a cycloalkylidene group.

[0104] The toner contains toner particles. The toner particles contain a binder resin (B) and wax. The wax contains a monoester compound represented by the following formula (3) (hereinafter, also simply referred to as "monoester compound").

[0105] R 31 -COO-R 32 (3)

[0106] Among them, R 31 and R 32 Each independently represents an alkyl group having 10 to 30 carbon atoms.

[0107] By containing the monoester compound, it is possible to provide an image forming apparatus and a process cartridge in which low-temperature fixability and environmental stability are simultaneously achieved.

[0108] When the ester compound in the wax consists only of compounds having at least two ester groups, the affinity between the wax and the binder resin (A) becomes too high, so that colorant adsorption is likely to occur, and adhesion of the wax to the photosensitive member may occur under a high temperature and high humidity environment, resulting in deterioration of image quality such as blank spots due to contamination of the photosensitive member.

[0109] In addition, when the wax does not have an ester group, the affinity with the binder resin (A) becomes too low, and the toner easily rolls when in contact with the medium during transfer under a high temperature and high humidity environment. As a result, the image clarity is lost and the image quality is deteriorated.

[0110] In the monoester compound, R in formula (3) 31 and R 32 The carbon numbers represented by R are each independently preferably from 15 to 25, and more preferably from 18 to 22. 31 and R 32 Can be the same or different.

[0111] The number of carbon atoms contained in one molecule of the monoester compound is preferably 36-44, and more preferably 38-42.

[0112] Examples of aliphatic alcohols that can be used to produce the monoester compound include 1-hexanol, 1-heptanol, 1-octanol, 1-nonanol, 1-decanol, undecanol, lauryl alcohol, myristyl alcohol, 1-hexadecanol, stearyl alcohol, arachidonic alcohol, behenyl alcohol, lignin alcohol, and the like.

[0113] Examples of aliphatic carboxylic acids that can be used to produce the monoester compound include valeric acid, caproic acid, heptanoic acid, caprylic acid, nonanoic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid, lignoceric acid, and the like.

[0114] Specific examples of the monoester compounds include behenyl stearate (C 17 H 35 -COO-C 22 H 45 ), Arachidyl arachidate (C 19 H39 -COO-C 20 H 41 ), stearyl behenate (C 21 H 43 -COO-C 18 H 37 ), behenyl behenate (C 21 H 43 -COO-C 22 H 45 ) and hexadecyl lignin (C 23 H 47 -COO-C 16 H 33 ) etc. Among these monoester compounds, behenyl stearate and stearyl behenate are more preferred.

[0115] When the wax contains the monoester compound represented by formula (3) as a main component, the effect of the present invention can be easily obtained. Specifically, the amount of the monoester compound in the wax is preferably 50% to 100% by mass, and more preferably 95% to 100% by mass.

[0116] In addition, the hydroxyl value of the monoester compound is preferably not more than 10 mgKOH / g, more preferably not more than 6 mgKOH / g, and further preferably not more than 3 mgKOH / g. The hydroxyl value may be, for example, at least 0.0 mgKOH / g. When the hydroxyl value is within the above range, storage stability is further improved.

[0117] In addition, the acid value of the monoester compound is preferably not more than 1.0 mgKOH / g, more preferably not more than 0.6 mgKOH / g, and further preferably not more than 0.3 mgKOH / g. The acid value may be, for example, at least 0.0 mgKOH / g. When the acid value is within the above range, storage stability is further improved.

[0118] The toner preferably contains the wax in an amount of 1.0 to 30.0 mass %, more preferably 1.0 to 20.0 mass %, and even more preferably 7.0 to 13.0 mass %. When the amount is at least 1.0 mass %, the effect of the present invention can be stably obtained. Meanwhile, when the amount is not more than 30.0 mass %, compatibility with storage stability can be achieved.

[0119] In addition, the wax may include other waxes besides the monoester compound.

[0120] Specific examples of other waxes include the following.

[0121] For example, aliphatic hydrocarbons such as low molecular weight polyethylene, low molecular weight polypropylene, microcrystalline wax, paraffin and Fischer-Tropsch wax; petroleum waxes such as caprolactam and their derivatives; montan wax and its derivatives; natural waxes such as carnauba wax and candelilla wax and their derivatives.

[0122] Here, the derivatives include oxides, block copolymers with vinyl monomers, and graft-modified products.

[0123] Furthermore, a diester compound including two ester bonds in one molecule and a polyfunctional ester compound including at least three ester bonds in one molecule may be used as other waxes.

[0124] Specific examples include the following compounds.

[0125] For example, pentaerythritol ester compounds such as pentaerythritol tetrapalmitate, pentaerythritol tetrabehenate and pentaerythritol tetrastearate; glycerol ester compounds such as hexaglycerol tetrabehenate tetrapalmitate, hexaglycerol octabehenate, pentaglycerol heptabehenate, tetraglycerol hexabehenate, triglycerol pentabehenate, diglycerol tetrabehenate and glycerol tribehenate; and dipentaerythritol ester compounds such as dipentaerythritol hexamyristate and dipentaerythritol hexapalmitate, etc.

[0126] In addition, other esters such as ethylene glycol dibehenate, ethylene glycol distearate, ethylene glycol arachidonic stearate, ethylene glycol stearyl palmitate, butylene glycol dibehenate, butylene glycol distearate, butylene glycol stearyl palmitate, butylene glycol dibehenate, pentaerythritol tetrastearate, pentaerythritol tetrapalmitate, pentaerythritol tetrabehenate, dipentaerythritol hexapalmitate, dipentaerythritol hexastearate, and dipentaerythritol hexabehenate, etc. may be used.

[0127] The melting point of the monoester compound is preferably 60°C to 80°C, and more preferably 65°C to 75°C.

[0128] By setting the above range, it becomes easy to achieve both storage stability and low-temperature fixability of the toner.

[0129] There is no particular limitation on the production method of the above monoester compound, and examples thereof include a synthesis method based on an oxidation reaction, a synthesis from carboxylic acid and its derivatives, an ester group introduction reaction represented by a Michael addition reaction, a method utilizing a dehydration condensation reaction of a carboxylic acid compound and an alcohol compound, a reaction from an acid halide and an alcohol compound, and an ester exchange reaction, etc.

[0130] In the production of these monoester compounds, a catalyst may be used appropriately. The catalyst is preferably an acidic or alkaline catalyst commonly used in esterification reactions, such as zinc acetate and titanium compounds. After the esterification reaction, the target product may be purified by recrystallization or distillation.

[0131] Specific production examples of the monoester compound are shown below, but are not limited to the following production examples.

[0132] First, the alcohol monomer and carboxylic acid monomer as raw materials are added to the reaction vessel. The molar ratio of the alcohol monomer and the carboxylic acid monomer is appropriately adjusted according to the chemical structure of the target monoester compound. That is, the alcohol monomer and the carboxylic acid monomer are mixed with the molar ratio of alcohol monomer:carboxylic acid monomer=1:1. Considering the reactivity in the dehydration condensation reaction, one of the alcohol monomer and the carboxylic acid monomer can be added to slightly exceed the above ratio.

[0133] Next, the mixture of alcohol monomer and carboxylic acid monomer is heated appropriately to carry out dehydration condensation reaction. Alkaline aqueous solution and appropriate organic solvent are added to the crude esterification product obtained by dehydration condensation reaction to deprotonate unreacted alcohol monomer and carboxylic acid monomer, and separate them in aqueous phase. Thereafter, monoester compound can be obtained by appropriately washing with water, distilling off solvent and filtering.

[0134] The affinity between the wax and the binder resin (A) can be numerically determined by Hansen solubility parameters (also referred to as "solubility parameters" for short).

[0135] The solubility parameter is a numerical value used as an indicator of the solubility or affinity of a substance, which indicates how much a substance dissolves in another substance. Substances with similar solubility parameters have high solubility and affinity, and those with different solubility parameters have low solubility and affinity.

[0136] The solubility parameters can be calculated by the solubility parameter calculation software Hansen Solubility Parameters in Practice 4th Edition 4.1.03 (available from https: / / www.hansen-solubility.com / HSPiP / ). The calculation method is based on the theory of Hansen solubility parameters. In the Hansen theory of solubility parameters, the energy of molecular evaporation is divided into three types of energy, namely, energy from dispersion forces (dispersion terms, also called D terms), energy from dipole interactions (polar terms, also called P terms), and energy from hydrogen bonds (hydrogen bond terms, also called H terms), and these are treated as three-dimensional vectors.

[0137] The solubility parameter is an index of affinity between the wax and the structure represented by formula (1) or (2) in the binder resin (A), and can be an index of the possibility of contamination of the photosensitive member. The adhesion of the wax can be compared by the magnitude relationship between the energy from the dispersion force (dispersion term) and the energy from the dipole interaction (polar term) of the wax and the structure represented by formula (1) or (2) in the binder resin (A).

[0138] The three-dimensional vector of solubility parameters is calculated by the following method.

[0139] (1): Using solubility parameter calculation software, Hansen solubility parameters (D term, P term, H term), molar volume, and molecular weight are calculated for each unit derived from each monomer as a precursor of a vinyl resin or polyester (hereinafter also referred to as a monomer unit).

[0140] For the monomer for the vinyl resin, calculation is performed in a state where an unknown halogen X which does not affect the calculation result is added to a double bond cleaved by polymerization as shown in the following formula (A).

[0141]

[0142] For a monomer for a compound having at least one ester bond, calculation is performed in a state where one of the functional groups in the monomer to be subjected to condensation reaction is changed to [-C(=O)OX] or [XC(=O)-O-] and the other functional group is replaced with X as shown in the following formula (B).

[0143]

[0144] For the monomer for the compound having at least one carbonate bond, calculation is performed in a state where one of the functional groups in the monomer to be subjected to condensation reaction is changed to [-OC(=O)OX] and the other functional group is replaced with X as shown in the following formula (C).

[0145]

[0146] For other monomers that condense by dehydration, when condensation is performed by, for example, a reaction represented by the following formula (D), the solubility parameter of each monomer is calculated in a state where one terminal of the monomer is composed of a bonding group J and X, and the other terminal is substituted with X as shown in the following formulas (E) and (F).

[0147] G-Ra-G+H-Rb-H→(Ra-J-Rb) n (D)

[0148] XJ-Ra-X (E)

[0149] XJ-Rb-X (F)

[0150] Among them, G and H are reactive functional groups, J is a bonding group, and Ra and Rb are organic groups.

[0151] (2): The molar volume ratio of the units derived from each monomer is calculated from the molar ratio of each monomer unit in the polymer and the molar volume ratio of each unit.

[0152] (3): The sum of the values ​​obtained by multiplying the molar volume by the D term of the Hansen solubility parameter of each monomer unit is taken as the D term of the Hansen solubility parameter of the polymer. The P term and the H term are calculated in the same manner.

[0153] In the case of a mixture of at least two substances from among the binder resin (A), the binder resin (B), and the wax, the method of finding the solubility parameter involves first finding the solubility parameter (D term, P term, H term) of each substance. Then, a value obtained by calculating the arithmetic mean of the parameters of the D term, P term, and H term of each substance is taken as the solubility parameter (D term, P term, H term) of the mixture.

[0154] When the dispersion term and polar term of the Hansen solubility parameter in wax are defined as SD2[(J / cm 3 ) 1 / 2 ] and SP2[(J / cm 3 ) 1 / 2 ], and the dispersion term and polar term of the Hansen solubility parameter in the structure shown in formula (2) in the binder resin (A) are respectively defined as SD(A2)[(J / cm 3 ) 1 / 2 ] and SP(A2)[(J / cm 3 ) 1 / 2 ], from the viewpoint of obtaining appropriate affinity, it is preferred to satisfy the following formulas (4) and (5).

[0155] 2.50≤SD(A2)-SD2≤5.00 (4)

[0156] 2.50≤SP(A2)-SP2≤6.00 (5)

[0157] When SD(A2)-SD2 is not greater than 5.00, affinity does not become too low, and the toner is less likely to roll when in contact with the medium during transfer under a high temperature and high humidity environment. As a result, the image clarity is less likely to be lost and the image quality tends not to deteriorate.

[0158] When SD(A2)-SD2 is at least 2.50, the affinity does not become too high, and the wax is less likely to adhere to the photosensitive member under a high temperature and high humidity environment. As a result, image quality degradation such as blank spots caused by contamination of the photosensitive member is less likely to occur.

[0159] When SP(A2)-SP2 is not greater than 6.00, affinity does not become too low, and the toner is less likely to roll when in contact with the medium during transfer under a high temperature and high humidity environment. As a result, the image clarity is less likely to be lost and the image quality tends not to deteriorate.

[0160] When SP(A2)-SP2 is at least 2.50, affinity does not become too high, and wax is less likely to adhere to the photosensitive member under a high temperature and high humidity environment. As a result, image quality degradation such as blank spots caused by contamination of the photosensitive member is less likely to occur.

[0161] SD(A2)-SD2 is preferably 3.00 to 4.00, and more preferably 3.30 to 3.80. SP(A2)-SP2 is preferably 2.70 to 5.00, and more preferably 3.00 to 4.50.

[0162] Furthermore, SD(A2) is preferably from 18.00 to 20.00, and more preferably from 19.00 to 19.50. SP(A2) is preferably from 3.00 to 6.00, and more preferably from 3.50 to 5.50.

[0163] Furthermore, SD2 is preferably 15.00 to 18.00, and more preferably 15.50 to 17.00. SP2 is preferably 0.00 to 2.00, and more preferably 0.50 to 1.50.

[0164] SD(A2) and SP(A2) can be controlled by changing the type and blending amount of the monomer having the structure represented by formula (2'). In addition, SD2 and SP2 can be controlled by changing the type of monomer as a raw material of the monoester compound in the wax, and the type and amount of the wax other than the monoester compound.

[0165] In the relationship between the photosensitive member and the toner, when the dispersion term and the polarity term of the Hansen solubility parameter of the structure represented by the formula (1) in the binder resin (A) are SD(A1)[(J / cm 3 ) 1 / 2 ] and SP(A1)[(J / cm 3 ) 1 / 2 ], from the viewpoint of obtaining appropriate affinity, it is preferred to satisfy the following formulas (6) and (7).

[0166] 2.50≤SD(A1)-SD2≤5.00 (6)

[0167] 2.50≤SP(A1)-SP2≤6.00 (7)

[0168] When SD(A1)-SD2 is not greater than 5.00, affinity does not become too low, and the toner is less likely to roll when in contact with the medium during transfer under a high temperature and high humidity environment. As a result, the image clarity is less likely to be lost and the image quality tends not to deteriorate.

[0169] When SD(A1)-SD2 is at least 2.50, affinity does not become too high, and wax is less likely to adhere to the photosensitive member under a high temperature and high humidity environment. As a result, image quality degradation such as blank spots caused by contamination of the photosensitive member is less likely to occur.

[0170] When SP(A1)-SP2 is not greater than 6.00, affinity does not become too low, and the toner is less likely to roll when in contact with a medium during transfer under a high temperature and high humidity environment. As a result, image clarity is less likely to be lost and image quality tends not to deteriorate.

[0171] When SP(A1)-SP2 is at least 2.50, affinity does not become too high, and wax is less likely to adhere to the photosensitive member under a high temperature and high humidity environment. As a result, image quality degradation such as blank spots caused by contamination of the photosensitive member is less likely to occur.

[0172] SD(A1)-SD2 is preferably 3.50 to 4.50, and more preferably 3.80 to 4.40. SP(A1)-SP2 is preferably 3.50 to 6.00, and more preferably 4.50 to 6.00.

[0173] In addition, SD(A1) is preferably 19.00 to 21.00, and more preferably 19.70 to 20.50. SP(A1) is preferably 4.00 to 7.50, and more preferably 5.00 to 7.00.

[0174] SD(A1) and SP(A1) can be controlled by changing the kind and amount of the monomer having a structure represented by formula (1').

[0175] The compatibility of the binder resin (B) and the wax can be compared from the magnitude relationship between the energy derived from the dispersion force (dispersion term D) and the energy derived from the dipole interaction (polar term P) of the wax and the binder resin (B).

[0176] Since the wax and the binder resin (B) have appropriate affinity, the low temperature fixability and storage stability of the toner are improved. Specifically, when the dispersion term and polarity term of the Hansen solubility parameter in the binder resin (B) are SD1[(J / cm 3 ) 1 / 2] and SP1[(J / cm 3 ) 1 / 2 ], it is preferred to satisfy the following formulas (8) and (9).

[0177] 0.00≤SD1-SD2≤3.00 (8)

[0178] 0.00≤SP1-SP2≤0.30 (9)

[0179] When SD1-SD2 is not more than 3.00, the affinity between the binder resin (B) and the wax does not become too low, and the plasticizing effect by the wax increases, so the low-temperature fixability is improved.

[0180] When SD1-SD2 is at least 0.00, the energy of the wax is relatively low and the wax is stabilized. As a result, the wax is less likely to ooze out to the toner surface layer, and the storage stability tends to be improved.

[0181] When SP1-SP2 is not more than 0.30, the affinity between the binder resin (B) and the wax does not become too low, and the plasticizing effect of the wax increases, so the low-temperature fixability is improved.

[0182] When SP1-SP2 is at least 0.00, the energy of the wax is relatively low and the wax is stabilized. As a result, the wax is less likely to ooze out to the toner surface layer under a high humidity environment, and storage stability tends to be improved.

[0183] SD1-SD2 is preferably 1.00 to 2.80, and more preferably 2.00 to 2.50. SP1-SP2 is preferably 0.10 to 0.25, and more preferably 0.15 to 0.25.

[0184] Furthermore, SD1 is preferably 17.00 to 21.00, and more preferably 18.00 to 20.50. SP1 is preferably 0.00 to 6.00, and more preferably 0.00 to 4.00.

[0185] SD1 and SP1 can be controlled by changing the kind and blending ratio of the monomers constituting the binder resin (B).

[0186] The toner particles have a core-shell structure having a core containing a binder resin (B) and a wax, and a shell layer formed on the surface of the core. Since the toner particles have a core-shell structure, the wax can be prevented from adhering to the photosensitive member, and high image quality can be maintained for a long time. A toner without a core-shell structure may cause contamination of the photosensitive member with the wax, resulting in deterioration of image quality.

[0187] Furthermore, the thickness of the shell is preferably no greater than 100 nm. More preferably, it is no greater than 50 nm. The thickness of the shell is preferably at least 1 nm.

[0188] The thickness of the shell layer can be analyzed by various analysis methods, and one example is shown below.

[0189] Measurement by time-of-flight secondary ion mass spectrometry: The depth at which the ratio of the signal from the shell layer to the signal from the core is 1:1 when performing depth profile measurement is taken as the thickness of the shell layer. The thickness of the shell layer can be controlled by the amount of the raw material for the shell layer added when producing the toner particles.

[0190] Electrophotographic photosensitive member

[0191] The production method of the photosensitive member can be exemplified by preparing a coating liquid for each layer described below, coating the coating liquid on a support in the order of the desired layers, and drying the coating liquid. At this time, examples of the coating method of the coating liquid include dip coating, spray coating, inkjet coating, roller coating, die coating, blade coating, curtain coating, wire rod coating, and ring coating, etc. Among them, dip coating is preferred from the viewpoint of efficiency and productivity.

[0192] Each layer is described below.

[0193] Support

[0194] The photosensitive member may have a support. The support is preferably a conductive support having conductivity. In addition, examples of the shape of the support include cylindrical, belt-shaped, and sheet-shaped. Among them, a cylindrical support is preferred. In addition, the surface of the support may be subjected to electrochemical treatment such as anodizing, or sandblasting and cutting treatment, etc.

[0195] For the support, materials such as metal, resin and glass are preferable.

[0196] Examples of the metal include aluminum, iron, nickel, copper, gold, stainless steel, and alloys thereof, etc. Among them, an aluminum support using aluminum is preferable.

[0197] Furthermore, conductivity may be imparted to the resin or glass by treatment such as mixing or coating with a conductive material.

[0198] Conductive layer

[0199] The conductive layer may be provided on the support. By providing the conductive layer, scratches and irregularities on the surface of the support can be shielded, and reflection of light on the surface of the support can be controlled.

[0200] The conductive layer preferably contains conductive particles and a resin.

[0201] Examples of the material of the conductive particles include metal oxides, metals, carbon black, and the like.

[0202] Examples of the metal oxide include zinc oxide, aluminum oxide, indium oxide, silicon oxide, zirconium oxide, tin oxide, titanium oxide, magnesium oxide, antimony oxide, bismuth oxide, and the like.

[0203] Examples of metals include aluminum, nickel, iron, nichrome, copper, zinc, silver, and the like.

[0204] Among them, it is preferable to use a metal oxide as the material of the conductive particles, and it is particularly preferable to use titanium oxide, tin oxide, or zinc oxide.

[0205] When a metal oxide is used as the material of the conductive particles, the surface of the metal oxide particles may be treated with a silane coupling agent or the like, or the metal oxide may be doped with an element such as phosphorus or aluminum or an oxide thereof.

[0206] Furthermore, the conductive particles may have a laminated structure including a core particle and a covering layer covering the particle. Examples of the material of the core particle include titanium oxide, barium sulfate, zinc oxide, etc. Examples of the material of the covering layer include metal oxides such as tin oxide.

[0207] When metal oxide particles are used as the conductive particles, the volume average particle diameter thereof is preferably 1 nm to 500 nm, and more preferably 3 nm to 400 nm.

[0208] Examples of the resin include polyester resins, polycarbonate resins, polyvinyl acetal resins, acrylic resins, silicone resins, epoxy resins, melamine resins, polyurethane resins, phenolic resins, alkyd resins, and the like.

[0209] In addition, the conductive layer may further include silicone oil, resin particles, and a shielding agent such as titanium oxide, and the like.

[0210] The average film thickness of the conductive layer is preferably 1 μm to 50 μm, and particularly preferably 3 μm to 40 μm.

[0211] The conductive layer can be formed by preparing a conductive layer coating liquid containing the above-mentioned materials and a solvent, forming a coating film, and drying. Examples of solvents suitable for the coating liquid include alcohol solvents, sulfoxide solvents, ketone solvents, ether solvents, ester solvents, and aromatic hydrocarbon solvents. Examples of dispersion methods for dispersing conductive particles in the conductive layer coating liquid include methods using a paint stirrer, a sand mill, a ball mill, and a liquid collision type high-speed disperser.

[0212] Base coating

[0213] The primer layer may be provided on the support or the conductive layer. By providing the primer layer, the adhesion function between the layers can be improved and the charge injection blocking function can be imparted.

[0214] The primer layer preferably contains a resin. The primer layer can be formed as a cured film by polymerizing a composition containing a monomer having a polymerizable functional group.

[0215] Examples of the resin include polyester resins, polycarbonate resins, polyvinyl acetal resins, acrylic resins, epoxy resins, melamine resins, polyurethane resins, phenolic resins, polyvinylphenolic resins, alkyd resins, polyvinyl alcohol resins, polyethylene oxide resins, polypropylene oxide resins, polyamide resins, polyamic acid resins, polyimide resins, polyamide-imide resins, cellulose resins, and the like.

[0216] Examples of the polymerizable functional group of the monomer having a polymerizable functional group include an isocyanate group, a blocked isocyanate group, a methylol group, an alkylated methylol group, an epoxy group, a metal alkoxide group, a hydroxyl group, an amino group, a carboxyl group, a thiol group, a carboxylic anhydride group, and a carbon-carbon double bond group.

[0217] In order to improve the electrical characteristics, the undercoat layer may further contain an electron transporting substance, a metal oxide, a metal, a conductive polymer, etc. Among them, it is preferable to contain an electron transporting substance and a metal oxide.

[0218] Examples of the electron transporting substance include quinone compounds, imide compounds, benzimidazole compounds, cyclopentadienyldiene compounds, fluorenone compounds, xanthone compounds, benzophenone compounds, cyanovinyl compounds, aryl halide compounds, silole compounds, and boron-containing compounds, etc. The undercoat layer can be formed into a cured film by using an electron transporting substance having a polymerizable functional group as the electron transporting substance and copolymerizing the electron transporting substance with the above-mentioned monomer having a polymerizable functional group.

[0219] Examples of the metal oxide include indium tin oxide, tin oxide, indium oxide, titanium oxide, zinc oxide, aluminum oxide, silicon dioxide, and the like.

[0220] Examples of metals include gold, silver, aluminum, and the like.

[0221] In addition, the undercoat layer may further contain additives.

[0222] The average film thickness of the undercoat layer is preferably 0.1 μm to 50 μm, more preferably 0.2 μm to 40 μm, and particularly preferably 0.3 μm to 30 μm.

[0223] The undercoat layer can be formed by preparing an undercoat layer coating solution comprising the above-mentioned materials and a solvent, forming a coating film, and drying and / or curing. Examples of solvents for the coating solution include alcohol solvents, ketone solvents, ether solvents, ester solvents, and aromatic hydrocarbon solvents.

[0224] Photosensitive layer

[0225] The photosensitive member may generally have a photosensitive layer. The photosensitive layer is preferably formed on a support, and a conductive layer and an undercoat layer may be provided between the support and the photosensitive layer. The photosensitive layer is mainly classified into (1) a single-layer type photosensitive layer and (2) a laminated type photosensitive layer.

[0226] (1) Single-layer type photosensitive layer It is possible to have, for example, a photosensitive layer containing a combination of a charge generating substance, a charge transporting substance, and an electron transporting substance.

[0227] (2) The laminated photosensitive layer may have, for example, a charge generating layer containing a charge generating substance and a charge transporting layer containing a charge transporting substance.

[0228] (1) Single-layer photosensitive layer

[0229] The photosensitive layer according to the present disclosure may be a single-layer photosensitive layer. The single-layer photosensitive layer may be formed, for example, by preparing a photosensitive layer coating solution containing a charge generating substance, a charge transporting substance, an electron transporting substance, a resin containing a binder resin (A), and a solvent, forming a coating film, and drying.

[0230] The single-layer type photosensitive layer may contain resins other than the binder resin (A) as long as the effects of the present disclosure are not impaired. Examples of resins other than the binder resin (A) include polycarbonate resins, styrene resins, acrylic resins, and the like.

[0231] Examples of the charge generating material include azo pigments, perylene pigments, polycyclic quinone pigments, indigo pigments, and phthalocyanine pigments, etc. Among them, azo pigments and phthalocyanine pigments are preferred. Among phthalocyanine pigments, metal-free phthalocyanine, oxytitanium phthalocyanine pigments, chlorogallium phthalocyanine pigments, and hydroxygallium phthalocyanine pigments are preferred.

[0232] Examples of charge transport materials include polycyclic aromatic compounds, heterocyclic compounds, hydrazone compounds, styryl compounds, enamine compounds, benzidine compounds, triarylamine compounds, and resins having groups derived from these substances. These charge transport materials can be used alone or in combination of at least two. Among them, triarylamine compounds and benzidine compounds are preferred.

[0233] Examples of electron transport substances include quinone compounds, imide compounds, hydrazone compounds, malononitrile compounds, thiopyran compounds, trinitrothioxanthone compounds, 3,4,5,7-tetranitro-9-fluorenone compounds, dinitroanthracene compounds, dinitroacridine compounds, tetracyanoethylene, 2,4,8-trinitrothioxanthone, dinitrobenzene, dinitroacridine, succinic anhydride, maleic anhydride, and dibromomaleic anhydride.

[0234] Examples of the quinone-based compounds include diphenylquinone-based compounds, azoquinone-based compounds, anthraquinone-based compounds, naphthoquinone-based compounds, nitroanthraquinone-based compounds, and dinitroanthraquinone-based compounds.

[0235] These electron transport substances may be used alone or in combination of at least two.

[0236] Among these electron transport substances, compounds represented by the following formulae (10) to (18) are preferable.

[0237]

[0238]

[0239] in,

[0240] R 41 To R 44 , R 51 , R 52 , R 61 , R 62 , R 71 To R 73 , R 101 , R 102 , and R 121 To R 124 Each independently represents a hydrogen atom or an alkyl group having 1 to 6 (preferably 1 to 4) carbon atoms.

[0241] R 63 represents a hydrogen atom, a halogen group or an alkyl group having 1 to 6 (preferably 1 to 4) carbon atoms,

[0242] R 74 , R 81 and R 82 each independently represents an alkyl group having 1 to 6 (preferably 1 to 4) carbon atoms, a halogen group, or a phenyl group having an alkyl group having 1 to 6 (preferably 1 to 4) carbon atoms,

[0243] R 91 represents an alkyl group having 1 to 6 (preferably 1 to 4) carbon atoms which may have a hydrogen atom or a halogen atom, and

[0244] R 111 and R 112 It represents an alkyl group having 1 to 6 (preferably 1 to 4) carbon atoms which may have a substituent, or a phenyl group which may have a substituent.

[0245] The content ratio (mass ratio) of the charge generating substance to the entire resin components in the photosensitive layer is preferably 1:1000 to 50:100, and more preferably 5:1000 to 30:100.

[0246] The content ratio (mass ratio) of the charge transporting substance to the entire resin components in the photosensitive layer is preferably 1:10 to 20:10, and more preferably 1:10 to 10:10.

[0247] The content ratio (mass ratio) of the electron transport substance to the entire resin components in the photosensitive layer is preferably 5:100 to 10:10, and more preferably 1:10 to 8:10.

[0248] In addition, the photosensitive layer may contain additives such as antioxidants, ultraviolet absorbers, plasticizers, leveling agents, slip imparting agents, and abrasion resistance improvers. Specific examples include hindered phenol compounds, hindered amine compounds, sulfur compounds, phosphorus compounds, benzophenone compounds, siloxane-modified resins, silicone oils, fluororesin particles, polystyrene resin particles, polyethylene resin particles, silica particles, aluminum oxide particles, and boron nitride particles.

[0249] In order to improve the durability of the photosensitive layer, silica particles may be contained.

[0250] The silica particles may be surface treated with a surface treatment agent. Examples of the surface treatment agent include hexamethyldisilazane, N-methyl-hexamethyldisilazane, hexamethyl-N-propyldisilazane, dimethyldichlorosilane, and polydimethylsiloxane. Hexamethyldisilazane is particularly preferred as the surface treatment agent.

[0251] The amount of the silica particles is preferably 0.5 to 15 parts by mass relative to 100 parts by mass of the binder resin (A).

[0252] The amount of the silica particles is preferably 0.5 parts by mass to 15 parts by mass, and more preferably 1 part by mass to 10 parts by mass, relative to 100 parts by mass of the entire resin components in the photosensitive layer.

[0253] The volume average particle size of the silica particles is preferably 7 nm to 1000 nm, and more preferably 10 nm to 300 nm. Identification of the silica particles and the volume average particle size of the silica particles can be confirmed by observing a cross section of the photosensitive layer using a scanning electron microscope (SEM) or the like.

[0254] The film thickness of the photosensitive layer is preferably 5 μm to 100 μm, and more preferably 10 μm to 50 μm.

[0255] The photosensitive layer can be formed by preparing a photosensitive layer coating solution comprising the above-mentioned material and a solvent, forming a coating film, and drying. Examples of solvents for the coating solution include alcohol solvents, ketone solvents, ether solvents, ester solvents, and aromatic hydrocarbon solvents. Among these solvents, ether solvents and aromatic hydrocarbon solvents are preferred.

[0256] (2) Laminated photosensitive layer

[0257] The photosensitive layer may be a laminated type photosensitive layer. The laminated type photosensitive layer may have, for example, a charge generating layer and a charge transporting layer.

[0258] The charge generating layer may contain a charge generating substance and a resin.

[0259] The charge transporting layer may contain a charge transporting substance and a resin including a binder resin (A).

[0260] As the charge generating substance, the charge transporting substance, and the resin, the same materials as exemplified in the above-mentioned "(1) Single-layer type photosensitive layer" can be used.

[0261] The amount of the charge generating substance in the charge generating layer is preferably 40% by mass to 85% by mass, and more preferably 60% by mass to 80% by mass, relative to the total mass of the charge generating layer.

[0262] The average film thickness of the charge generating layer is preferably from 0.1 μm to 1 μm, and more preferably from 0.15 μm to 0.4 μm.

[0263] The amount of the charge transporting substance in the charge transporting layer is preferably 25% by mass to 70% by mass, and more preferably 30% by mass to 55% by mass, relative to the total mass of the charge transporting layer.

[0264] The content ratio (mass ratio) of the charge transporting substance to the resin is preferably 4:10 to 20:10, and more preferably 5:10 to 12:10.

[0265] In addition, the same additives as exemplified in the above-mentioned "(1) Single-layer type photosensitive layer" may be included.

[0266] The average film thickness of the charge transport layer is preferably from 5 μm to 50 μm, more preferably from 8 μm to 40 μm, and particularly preferably from 10 μm to 30 μm.

[0267] Processing cartridge, image forming device

[0268] The processing box has

[0269] an electrophotographic photosensitive member, and

[0270] a developing device having a toner and supplying the toner onto the electrophotographic photosensitive member,

[0271] The electrophotographic photosensitive member has a surface layer containing a binder resin (A), and

[0272] The toner is the above-mentioned toner.

[0273] The process cartridge may be detachably mounted to a main body of the image forming apparatus.

[0274] The process cartridge may have at least one selected from the group consisting of a charging device, an image forming device, a transfer device, and a cleaning device, as necessary.

[0275] In addition, the image forming apparatus has

[0276] an electrophotographic photosensitive member, and

[0277] a developing device having a toner and supplying the toner onto the electrophotographic photosensitive member,

[0278] The electrophotographic photosensitive member has a surface layer containing a binder resin (A), and

[0279] The toner is the above-mentioned toner.

[0280] The image forming apparatus may have at least one selected from the group consisting of a charging device, an image forming device, a transfer device, a cleaning device, and a developing device, as necessary.

[0281] Figure 1 One example of a schematic configuration of an image forming apparatus having a process cartridge equipped with an electrophotographic photosensitive member is shown.

[0282] Reference numeral 1 denotes a cylindrical electrophotographic photosensitive member, which is rotationally driven in the direction of an arrow at a predetermined peripheral speed about an axis 2. The surface of the electrophotographic photosensitive member 1 is charged to a predetermined positive potential or negative potential by a charging device 3. Figure 1 A roller charging method using a roller-type charging member is shown, but a charging method such as a corona charging method, a proximity charging method, or an injection charging method may also be adopted.

[0283] The surface of the charged electrophotographic photosensitive member 1 is irradiated with exposure light 4 from an exposure device (not shown), and an electrostatic latent image corresponding to target image information is formed. The electrostatic latent image formed on the surface of the electrophotographic photosensitive member 1 is developed with a toner contained in a developing device 5, and a toner image is formed on the surface of the electrophotographic photosensitive member 1. The toner image formed on the surface of the electrophotographic photosensitive member 1 is transferred to a transfer material 7 by a transfer device 6. The transfer material 7 to which the toner image is transferred is conveyed to a fixing device 8, undergoes a fixing process of the toner image, and is printed out to the outside of the electrophotographic apparatus.

[0284] The image forming apparatus may have a cleaning device 9 for removing attached matters such as toner remaining on the surface of the electrophotographic photosensitive member 1 after transfer. Alternatively, a so-called cleaner-less system may be used in which the attached matters are removed by a developing device or the like without separately providing a cleaning device. The image forming apparatus may have a charge removal mechanism for eliminating the charge on the surface of the electrophotographic photosensitive member 1 with pre-exposure light 10 from a pre-exposure device (not shown). In addition, a guide device 12 such as a guide rail may be provided so that the process cartridge 11 can be mounted to / detached from the main body of the image forming apparatus.

[0285] The electrophotographic photosensitive member can be used in a laser beam printer, an LED printer, a copying machine, a facsimile device, a combination thereof, and the like.

[0286] In a cross section of a toner particle observed using a transmission electron microscope,

[0287] The waxes were observed as domains, and among them

[0288] The sum of the areas occupied by the domains in the entire cross section is defined as Wp,

[0289] The sum of the areas occupied by the domains in the region bounded by the outline of the cross section and the line dividing the region 0.1 μm inside the outline of the cross section is defined as Ws, and

[0290] When the sum of the areas occupied by domains in the inner region inside the line dividing the region within 0.1 μm inside the outline of the cross section is defined as Wc,

[0291] The ratio of Ws to Wp (Ws / Wp) is preferably 0.0 to 10.0%.

[0292] By controlling Ws / Wp within this range, the amount of wax present near the toner surface is reduced, and the amount of wax present on the toner particle surface under a high temperature and high humidity environment is reduced, so that good satisfactory image quality is obtained. When Ws / Wp is not more than 10.0%, an increase in the amount of wax present near the toner surface layer due to exudation of wax in the toner under a high temperature and high humidity environment is less likely to occur. As a result, contamination of the electrophotographic photosensitive member and rolling during transfer are less likely to occur, and image quality is less likely to deteriorate. Ws / Wp is more preferably 0.1 to 7.0%.

[0293] Ws / Wp can be controlled by the amount of wax in the toner and the thickness of the shell layer.

[0294] In addition, the ratio of Ws to Wc (Ws / Wc) is 0.00 to 0.50%. By controlling the ratio within this range, the amount of wax present near the surface layer of the toner particle is relatively less than the amount of wax present near the center, and while maintaining low-temperature fixability, durability and storage stability under high temperature and high humidity environments can be improved.

[0295] When Ws / Wc is not more than 0.50%, the amount of wax near the surface of the toner particles is relatively small, the plasticizing effect of the toner is improved, and the durability and storage stability under a high temperature and high humidity environment are improved.

[0296] Ws / Wc is preferably 0.01 to 0.30%. By separating Wc and Ws from the profile of the cross section of the toner particle by a distance of 0.1 μm, it becomes possible to compare the amount of wax near the shell layer and the amount of wax in the core, and by setting Ws / Wc within the above range, it can be shown that the amount of wax in the shell layer is relatively small.

[0297] Ws / Wc can be controlled by the amount of wax added to the toner, the thickness of the shell layer, and the like.

[0298] The shell layer of the toner particles preferably includes a vinyl resin including a monomer unit derived from methyl methacrylate. By including a monomer unit derived from methyl methacrylate, the surface of the toner particles can be positively charged, thereby facilitating use in an image forming apparatus using a positively charged toner.

[0299] In addition, in the secondary ion depth distribution measurement of the surface of the toner by time-of-flight secondary ion mass spectrometry (TOF-SIMS),

[0300] When the secondary ion intensities derived from the wax and the vinyl resin at a depth of t [nm] from the surface of the toner are defined as Iw(t) and Ib(t), respectively, the following formulas (19) and (20) are satisfied in the range of 0≤t≤10.

[0301] Iw(t) <Ib(t) (19)

[0302] Iw(t)<0.005 (20)

[0303] By satisfying the above formulas (19) and (20), the amount of wax in the toner surface layer can be suppressed, and good durability and storage stability can be maintained in a high-temperature and high-humidity environment. When Iw(t) < Ib(t), the amount of wax present in the toner surface layer can be reduced. As a result, contamination of the photoreceptor member and rolling during transfer are less likely to occur, and image quality is less likely to deteriorate. In addition, when Iw(t) < 0.005, the amount of wax present in the toner surface layer can be reduced, and as a result, contamination of the photoreceptor member or rolling during transfer is less likely to occur, and image quality is less likely to deteriorate. Iw(t) is more preferably Iw(t) < 0.003. Iw(t) can be set, for example, as Iw(t) ≥ 0.000.

[0304] For example, formulas (19) and (20) can be controlled by changing the type and amount of wax to be added, the thickness of the shell layer, and the like.

[0305] Hereinafter, the toner used in the present disclosure will be further described.

[0306] There is no particular limitation on the toner as long as it contains toner particles having a core-shell structure and the toner particles contain a monoester compound represented by formula (3), and there is no particular limitation on the method for producing the toner.

[0307] Toner particles can also be produced by a pulverization method, and toner particles can also be produced by methods for producing toner particles in an aqueous medium such as a dispersion polymerization method, an associative aggregation method, a dissolution suspension method, an emulsion aggregation method, and the like.

[0308] However, from the viewpoints of controlling the existence state of the monoester compound and constructing the core-shell structure, a method for producing toner particles in an aqueous medium is preferred, and from the viewpoint of toner shape control, it is more preferred to produce toner particles by a suspension polymerization method.

[0309] The suspension polymerization method will be described below.

[0310] In the suspension polymerization method, a polymerizable monomer composition is obtained by uniformly dissolving or dispersing a polymerizable monomer and wax (and optionally, a colorant, a polymerization initiator, a crosslinking agent, a charge control agent, and other additives). Then, the polymerizable monomer composition is dispersed in a continuous layer (for example, an aqueous phase) containing a dispersant by using a suitable stirrer to simultaneously cause a polymerization reaction, thereby obtaining toner particles having a desired particle diameter. The toner particles obtained by this suspension polymerization method (hereinafter, also referred to as "polymerized toner particles") have a substantially spherical shape of a single toner particle, so that the distribution of the charge amount is relatively uniform. Therefore, an improvement in image quality can be expected.

[0311] Given below are examples of the polymerizable monomer constituting the polymerizable monomer composition in the production of the polymerized toner particles.

[0312] Monovinyl monomers are preferably used as polymerizable monomers. Examples of monovinyl monomers include styrene; styrene derivatives such as vinyl toluene and α-methylstyrene; acrylic acid and methacrylic acid; acrylates such as methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, and dimethylaminoethyl acrylate; methacrylates such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, and dimethylaminoethyl methacrylate; nitrile compounds such as acrylonitrile and methacrylonitrile; amide compounds such as acrylamide and methacrylamide; olefins such as ethylene, propylene, and butene.

[0313] The monovinyl monomer preferably comprises at least one selected from the group consisting of styrene, styrene derivatives, acrylates and methacrylates. More preferably, the monovinyl monomer comprises at least one selected from the group consisting of styrene and styrene derivatives, and at least one selected from the group consisting of acrylates and methacrylates.

[0314] These monovinyl monomers may be used alone or in combination of at least two.

[0315] The polymerizable monomer preferably contains a monovinyl monomer as a main component. Specifically, the amount of the monovinyl monomer in the polymerizable monomer is preferably 50% by mass to 100% by mass.

[0316] Examples of the polymerization initiator used when producing toner particles by polymerization include persulfates such as potassium persulfate and ammonium persulfate; azo compounds such as 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-methyl-N-(2-hydroxyethyl)propionamide), 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis(2,4-dimethylvaleronitrile), and 2,2'-azobisisobutyronitrile; organic peroxides such as di-tert-butyl peroxide, benzoyl peroxide, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxydiethylacetate, tert-hexyl peroxy-2-ethylbutyrate, diisopropyl peroxydicarbonate, di-tert-butyl peroxyisophthalate, and tert-butyl peroxyisobutyrate; etc. These may be used alone or in combination of at least two. Among them, organic peroxides are preferably used because the amount of residual polymerizable monomers can be reduced and printing durability is excellent.

[0317] Among the organic peroxides, peroxy esters are preferred because of good initiator efficiency and also because the amount of residual polymerizable monomers can be reduced, and non-aromatic peroxy esters, ie, peroxy esters having no aromatic ring are more preferred.

[0318] As described above, the polymerization initiator may be added after the polymerizable monomer composition is dispersed in the aqueous medium and before droplets are formed, but the polymerization initiator may also be added to the monomer composition before being dispersed in the aqueous medium.

[0319] The addition amount of the polymerization initiator used for polymerization of the polymerizable monomer composition is preferably 0.1 to 20 parts by mass, more preferably 0.3 to 15 parts by mass, and particularly preferably 1 to 10 parts by mass relative to 100 parts by mass of the polymerizable monomer.

[0320] A crosslinking agent may be added when toner particles are produced by a polymerization method. The crosslinking agent is preferably added in an amount of 0.001 parts by mass to 15 parts by mass relative to 100 parts by mass of the polymerizable monomer.

[0321] Compounds having at least two polymerizable double bonds are mainly used as crosslinking agents. Specific examples include aromatic divinyl compounds such as divinylbenzene, divinylnaphthalene, and derivatives thereof; ester compounds in which at least two carboxylates having carbon-carbon double bonds are bonded to an alcohol having at least two hydroxyl groups such as ethylene glycol dimethacrylate and diethylene glycol dimethacrylate; other divinyl compounds such as N,N-divinylaniline and divinyl ether; and compounds having at least three vinyl groups; etc.

[0322] These cross-linking agents may be used alone or in combination of at least two.

[0323] Furthermore, the toner particles may contain a colorant. When a color toner is produced, black, cyan, yellow, and magenta colorants may be used.

[0324] As the black colorant, for example, carbon black and titanium black, and magnetic powders such as zinc iron oxide, and nickel iron oxide can be used.

[0325] As the cyan colorant, for example, copper phthalocyanine compounds and derivatives thereof, anthraquinone compounds, etc. can be used. Specific examples include CI Pigment Blue 2, 3, 6, 15, 15:1, 15:2, 15:3, 15:4, 16, 17:1, and 60, etc.

[0326] As yellow colorants, for example, compounds such as monoazo pigments, disazo pigments, azo pigments, and condensed polycyclic pigments can be used. Specific examples include CI Pigment Yellow 3, 12, 13, 14, 15, 17, 62, 65, 73, 74, 83, 93, 97, 120, 138, 155, 180, 181, 185, 186, and 213.

[0327] As the magenta colorant, for example, azo pigments such as monoazo pigments and disazo pigments and condensed polycyclic pigments can be used. Specific examples include CI Pigment Red 31, 48, 57:1, 58, 60, 63, 64, 68, 81, 83, 87, 88, 89, 90, 112, 114, 122, 123, 144, 146, 149, 150, 163, 170, 184, 185, 187, 202, 206, 207, 209, 237, 238, 251, 254, 255, 269 and CI Pigment Violet 19.

[0328] Each colorant may be used alone or in combination of at least two kinds thereof. The amount of the colorant is preferably 1 part by mass to 10 parts by mass relative to 100 parts by mass of the polymerizable monomer.

[0329] As other additives, a positively or negatively chargeable charge control agent may be used to improve the charging performance of the toner.

[0330] There is no particular limitation on the charge control agent as long as it is a charge control agent generally used for toners. Among the charge control agents, positively or negatively charged charge control resins are preferred because of their high compatibility with polymerizable monomers and because they can impart stable charging properties (charging stability) to toner particles. In addition, from the viewpoint of obtaining a positively charged toner, it is more preferred to use a positively charged charge control resin.

[0331] Examples of positively chargeable charge control agents include nigrosine dyes, quaternary ammonium salts, triaminotriphenylmethane compounds, imidazole compounds, and polyamine resins preferably used as charge control resins, and copolymers containing quaternary ammonium groups, and copolymers containing quaternary ammonium salt groups, etc. Examples of commercially available charge control resins include FCA-592P manufactured by Fujikura Kasei Co., Ltd.

[0332] Examples of negatively charged charge control agents include azo dyes containing metals such as Cr, Co, Al, and Fe, salicylic acid metal compounds, and alkyl salicylic acid metal compounds, as well as sulfonic acid group-containing copolymers, sulfonate group-containing copolymers, carboxylic acid group-containing copolymers, and carboxylate group-containing copolymers as charge control resins that are preferably used.

[0333] The charge control agent is preferably used in an amount of 0.01 to 10 parts by mass, more preferably 0.03 to 8 parts by mass, relative to 100 parts by mass of the polymerizable monomer. When the charge control agent is added in an amount of at least 0.01 parts by mass, fogging is less likely to occur. Meanwhile, when the charge control agent is added in an amount of not more than 10 parts by mass, print smudges are less likely to occur.

[0334] In addition, as other additives, it is preferable to use a molecular weight modifier when polymerizing the polymerizable monomer to be polymerized to form the binder resin.

[0335] There is no particular limitation on the molecular weight modifier as long as it is a molecular weight modifier generally used for toners. Examples thereof include mercaptans such as tert-dodecyl mercaptan, n-dodecyl mercaptan, n-octyl mercaptan, and 2,2,4,6,6-pentamethylheptane-4-mercaptan; thiuram disulfides such as tetramethylthiuram disulfide, tetraethylthiuram disulfide, tetrabutylthiuram disulfide, N,N'-dimethyl-N,N'-diphenylthiuram disulfide, and N,N'-dioctadecyl-N,N'-diisopropylthiuram disulfide; and the like. These molecular weight modifiers may be used alone or in combination of at least two.

[0336] The molecular weight modifier is preferably used in an amount of 0.01 parts by mass to 10 parts by mass, and more preferably 0.1 parts by mass to 5 parts by mass, relative to 100 parts by mass of the polymerizable monomer.

[0337] In the method of producing toner particles by polymerization, generally, the raw materials of the above-mentioned toner particles are appropriately added and uniformly dissolved or dispersed by a disperser such as a homogenizer, a ball mill, or an ultrasonic disperser to obtain a polymerizable monomer composition suspended in an aqueous medium containing a dispersant. At this time, in the case of obtaining toner particles of a desired size using a high-speed disperser such as a high-speed stirrer or an ultrasonic disperser, the particle diameter of the obtained toner particles becomes narrower.

[0338] Regarding the timing of adding the polymerization initiator, it can be added at the same time as other additives are added to the polymerizable monomer, or it can be mixed immediately before the polymerizable monomer composition is suspended in the aqueous medium. In addition, the polymerization initiator dissolved in the polymerizable monomer or the solvent can be added immediately after granulation and before starting the polymerization reaction.

[0339] After granulation, a conventional agitator may be used to perform agitation so as to maintain the granular state and prevent the granules from floating or settling.

[0340] When the toner particles are manufactured, known surfactants, organic dispersants, and inorganic dispersants can be used as dispersants. Among them, since the steric hindrance of the inorganic dispersant ensures dispersion stability, the stability is less likely to deteriorate even when the reaction temperature changes, and it is easy to wash and less likely to adversely affect the toner, so it is preferred to use an inorganic dispersant. Examples of such inorganic dispersants include sulfates such as barium sulfate and calcium sulfate; carbonates such as barium carbonate, calcium carbonate, and magnesium carbonate; phosphates such as calcium phosphate; metal oxides such as aluminum oxide and titanium oxide; and metal hydroxides such as aluminum hydroxide, magnesium hydroxide, sodium hydroxide, and iron hydroxide; etc.

[0341] It is desirable to use these inorganic dispersants in an amount of 0.2 to 20 parts by mass relative to 100 parts by mass of the polymerizable monomer. The above dispersants can be used alone or in combination of two or more. In addition, 0.001 to 0.1 parts by mass of surfactants can be used in combination with them.

[0342] In the step of polymerizing the above-mentioned polymerizable monomer, the polymerization temperature is preferably at least 50° C., and more preferably 60° C. to 95° C. The reaction time of the polymerization is preferably 1 hour to 20 hours, and more preferably 2 hours to 15 hours.

[0343] The toner particles are so-called core-shell type (or also referred to as "capsule type") polymer particles obtained by using polymer particles as a core layer and forming a shell layer different from the core layer on the outside of the core layer. For core-shell type polymer particles, the reduction of fixing temperature and the prevention of aggregation during storage can be balanced by coating a core layer made of a substance with a low softening point with a substance with a higher softening point.

[0344] There is no particular limitation on the method for producing core-shell type polymer particles using the above polymer particles, and a generally known method can be used. Among them, an in-situ polymerization method and a phase separation method are preferred from the viewpoint of production efficiency.

[0345] A method for producing core-shell type polymer particles by an in-situ polymerization method will be described below.

[0346] The core-shell type polymer particles can be obtained by adding a polymerizable monomer for forming a shell layer (polymerizable monomer for shell) and a polymerization initiator to an aqueous medium in which the polymer particles are dispersed and performing polymerization.

[0347] The same polymerizable monomers as those described above can be used as the polymerizable monomer for the shell. Among them, monomers such as styrene, acrylonitrile and methyl methacrylate that allow a polymer having a glass transition temperature (Tg) greater than 80° C. are preferably used alone or in combination of at least two. Among them, at least methyl methacrylate is preferably used as the polymerizable monomer for the shell.

[0348] Examples of polymerization initiators for polymerization of polymerizable monomers for shells include water-soluble polymerization initiators, for example, persulfate metal salts such as potassium persulfate and ammonium persulfate; and azo initiators such as 2,2'-azobis(2-methyl-N-(2-hydroxyethyl)propionamide), 2,2'-azobis-(2-methyl-N-(1,1-bis(hydroxymethyl)2-hydroxyethyl)propionamide), 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine], and hydrates thereof; etc. These can be used alone or in combination of at least two. The amount of the polymerization initiator is preferably 0.1 to 30 parts by mass, and more preferably 1 to 20 parts by mass, relative to 100 parts by mass of the polymerizable monomers for shells.

[0349] When the phase separation method is used, it is preferred to add a polymer obtained by polymerizing a shell-forming substance in advance to the polymerizable monomer for forming the core. When a prepolymerized polymer is used, a reactive polymer having an unsaturated bond is more preferred.

[0350] The polymerization temperature of the shell layer is preferably at least 50° C., and more preferably 60 to 95° C. The reaction time of the polymerization is preferably 1 to 20 hours, and more preferably 2 to 15 hours.

[0351] If necessary, the toner particles can also be obtained by filtering, washing and drying the obtained polymer particles by a known method. In addition, if necessary, a classification step can be added to cut the coarse powder or fine powder contained in the toner particles.

[0352] The obtained toner particles can be used as they are as a toner. In addition, as necessary, a toner can be obtained by mixing an external additive with the toner particles to attach the external additive to the surface of the toner particles.

[0353] There is no particular limitation on the agitator used for the mixing process, as long as the external additive can be attached to the surface of the toner particles. For example, an agitator capable of mixing and stirring such as FM mixer (trade name, manufactured by Nippon Coke Industry Co., Ltd.), SUPER mixer (trade name, manufactured by Kawada Manufacturing Co., Ltd.), Q mixer (trade name, manufactured by Nippon Coke Industry Co., Ltd.), MECHANOFUSION system (trade name, manufactured by Hosokawa Micron Co., Ltd.) and MECHANOMILL (trade name, manufactured by Okada Seiko Co., Ltd.) can be used for the external addition process.

[0354] Examples of the external additive include inorganic fine particles such as silica, titanium oxide, aluminum oxide, zinc oxide, tin oxide, calcium carbonate, calcium phosphate, and cerium oxide; and organic fine particles such as polymethyl methacrylate resin, silicone resin, and melamine resin; etc. Among them, inorganic fine particles are preferred, and among the inorganic fine particles, silica and titanium oxide are preferred, and silica is more preferred.

[0355] These external additives may be used alone or in combination of at least two.

[0356] The amount of the external additive is preferably 0.05 parts by mass to 6 parts by mass, and more preferably 0.2 parts by mass to 5 parts by mass, relative to 100 parts by mass of the toner particles.

[0357] The glass transition temperature (Tg) of the toner is preferably 45.0°C to 65.0°C, and more preferably 50.0°C to 65.0°C.

[0358] In the case where the glass transition temperature of the toner is within the above range, both storage stability and low temperature fixability can be achieved at a high level. The glass transition temperature can be controlled by the composition of the binder resin, the kind of the crystalline polyester, the molecular weight of the binder resin, and the like.

[0359] The volume average particle diameter (Dv) of the toner is preferably 3.00 μm to 9.00 μm, and more preferably 5.00 μm to 8.00 μm.

[0360] By setting the volume average particle diameter (Dv) of the toner within the above range, it is possible to improve the operability of the toner while sufficiently satisfying the dot reproducibility.

[0361] The ratio (Dv / Dn) of the volume average particle diameter (Dv) of the toner to the number average particle diameter (Dn) thereof is preferably not more than 1.25, and more preferably less than 1.25.

[0362] The Dv and Dv / Dn of the toner can be controlled by the amount of the dispersant, the type of the agitator, the rotation speed, and the like.

[0363] The average circularity of the toner is preferably at least 0.960, and more preferably at least 0.970. The upper limit of the average circularity is not particularly limited, but, for example, is not more than 1.000.

[0364] By setting the average circularity within the above range, the fluidity of the toner is improved, and it becomes possible to reduce the degradation of the toner during long-term printing. The average circularity can be controlled by the amount of the material forming the shell layer and the amount of the dispersant used, and the like.

[0365] The number average molecular weight (Mn) of the binder resin (B) is preferably 5,000 to 20,000, more preferably 7,000 to 20,000, and even more preferably 8,000 to 20,000. When the number average molecular weight of the binder resin (B) is not more than 20,000, low temperature fixability tends to be improved. When the number average molecular weight of the binder resin (B) is at least 5,000, heat resistant storage stability tends to be improved.

[0366] The weight average molecular weight (Mw) of the binder resin (B) is preferably 10,000 to 300,000, more preferably 15,000 to 260,000, and even more preferably 20,000 to 230,000. When the weight average molecular weight of the binder resin (B) is not more than 300,000, low temperature fixability tends to be improved. When the weight average molecular weight of the binder resin (B) is at least 10,000, heat resistant storage stability tends to be improved.

[0367] The molecular weight distribution (Mw / Mn) of the binder resin (B) is preferably 2 to 40, more preferably 3 to 35, and even more preferably 3 to 23. When the molecular weight distribution is not more than 40, low temperature fixability and storage stability tend to be improved. When the molecular weight distribution is at least 2, hot offset resistance tends to be improved.

[0368] Disclosure of analysis

[0369] The measurement methods of physical property values ​​according to the present disclosure are described below.

[0370] Volume average particle size Dv and particle size distribution Dv / Dn of toner

[0371] The volume average particle diameter Dv, number average particle diameter Dn, and particle diameter distribution Dv / Dn of the toner are measured by a particle size measuring device (Beckman Coulter, Inc., trade name: Multisizer). The measurement is performed with the Multisizer under the conditions of an opening diameter of 100 μm, a dispersion medium of Isoton II (trade name), a concentration of 10%, and a measured particle number of 100,000.

[0372] Specifically, 0.2 g of the toner was put into a beaker, and an alkylbenzenesulfonic acid aqueous solution (manufactured by Fujifilm Corporation, trade name: Drywell) was added to the beaker. Then, 2 mL of a dispersion medium was further added to wet the toner, 10 mL of the dispersion medium was added, and dispersion was performed for 1 minute by an ultrasonic disperser, and then measured with a particle size measuring instrument.

[0373] Method for measuring the melting point of wax

[0374] A total of 6 mg to 8 mg of the wax was weighed in a sample holder, and measured with a differential scanning calorimeter (manufactured by Seiko Instruments Inc., trade name: RDC-220) under the condition of heating from -200°C to 1000°C at 100°C / min to obtain a DSC curve. The peak temperature of the endothermic peak of the DSC curve was taken as the melting point.

[0375] Method for measuring glass transition temperature of toner

[0376] The glass transition temperature of the toner is measured according to ASTM D3418-97.

[0377] Specifically, 10 mg of the toner obtained by drying was accurately weighed and placed in an aluminum pan. An empty aluminum pan was used as a reference. A differential scanning calorimeter (manufactured by SII NanoTechnology Inc., trade name: DSC6220) was used to measure the glass transition temperature of the accurately weighed toner according to ASTM D 3418-97, in a temperature range of 0° C. to 150° C., at a temperature rise rate of 10° C. / min.

[0378] Method for measuring weight average molecular weight (Mw) and peak molecular weight (Mp) of resins, etc.

[0379] The weight average molecular weight (Mw) and the peak molecular weight (Mp) of the resin are measured by using gel permeation chromatography (GPC) in the following manner.

[0380] (1) Preparation of measurement samples

[0381] Sample and tetrahydrofuran (THF) are mixed to concentration of 5.0 mg / mL, the mixture is placed at room temperature for 5 to 6 hours, then fully vibrated, and THF and sample are mixed well until there is no aggregate of sample. Further the mixture is allowed to stand at room temperature for 12 hours. The time from sample and THF starting to mix to standing end is set to at least 72 hours, to obtain the component soluble in tetrahydrofuran (THF) of the sample.

[0382] Thereafter, a sample solution is obtained by filtering with a solvent-resistant membrane filter (pore diameter of 0.45 μm to 0.50 μm, Maishori Disc H-25-2, manufactured by Tosoh Corporation).

[0383] (2) Sample measurement

[0384] The measurement was performed under the following conditions by using the obtained sample solution.

[0385] Apparatus: High-speed GPC apparatus LC-GPC 150C (manufactured by Waters Corp.)

[0386] Column: Shodex GPC KF-801, 802, 803, 804, 805, 806, 807 (manufactured by Showa Denko KK) 7-column

[0387] Mobile phase: THF

[0388] Flow rate: 1.0mL / min

[0389] Column temperature: 40°C

[0390] Sample injection volume: 100 μL

[0391] Detector: RI (refractive index) detector

[0392] When the molecular weight of a sample is measured, the molecular weight distribution of the sample is calculated from the relationship between the counts and logarithmic values ​​of a calibration curve prepared using several monodisperse polystyrene standard samples.

[0393] The standard polystyrene samples used to create the calibration curve were manufactured by Pressure Chemical Co. or Toyo Soda Kogyo Co., Ltd. and had a molecular weight of 6.0×10 2 , 2.1×10 3 4.0×10 3 , 1.75×10 4 , 5.1×10 4 , 1.1×10 5 , 3.9×10 5 , 8.6×10 5 , 2.0×10 6 , and 4.48×10 6 .

[0394] Method for measuring the area occupied by wax domains in a cross section of a toner using a transmission electron microscope

[0395] A cross section of the toner was observed with a transmission electron microscope (TEM) and the evaluation of the wax domain was performed in the following manner.

[0396] Crystalline materials with clear contrast can be obtained by ruthenium staining of the toner cross section. Crystalline materials stain weaker than amorphous materials. This is apparently because the penetration of the dyeing material into the crystalline material is weaker than into the amorphous material due to differences in density, etc.

[0397] The amount of ruthenium atoms varies depending on the intensity of staining, so there are many ruthenium atoms in the strongly stained part, the electron beam is difficult to penetrate, and the part becomes black on the observed image. At the same time, in the weakly stained part, there are fewer ruthenium atoms, the electron beam is easy to penetrate, and the part becomes white on the observed image. In addition, among the crystalline materials contained in the toner, polymer crystals such as crystalline polyester and low molecular crystals such as wax can be distinguished by crystal structure. Specifically, in the case of polymer crystals, it is confirmed that there is a layered structure on the observed image, and in the case of low molecular crystals, it is confirmed that there is no layered structure on the observed image.

[0398] After an osmium film (5 nm) and a naphthalene film (20 nm) were applied to the toner as a protective film using an osmium plasma coater (Filgen, Inc., OPC80T), and the toner was embedded in a photocurable resin D800 (JEOL Ltd.), an ultrasonic ultramicrotome (Leica, UC7) was used to produce a toner cross-section with a film thickness of 60 nm at a cutting speed of 1 mm / s.

[0399] The obtained cross section was stained for 15 minutes in a RuO 4 atmosphere of 500 Pa by using a vacuum electron staining apparatus (VSC4R1H, manufactured by Filgen, Inc.), and STEM observation was performed using the STEM mode of TEM (manufactured by JEOL Ltd., JEM2800).

[0400] The STEM probe size was 1 nm, and the image size was 1024 pixels x 1024 pixels.

[0401] The obtained image was binarized (threshold value was 120 / 255) using image processing software "Image-Pro Plus" (manufactured by Media Cybernetics, Inc.). Crystal domains can be extracted by binarization. It should be noted that crystals that spanned the boundary (existed on the boundary) of 0.1 μm from the surface of the toner were not measured.

[0402] A line dividing the area within 0.1 μm inside the surface (profile of the cross section) of the toner particle is drawn, and the sum Ws of the area occupied by the wax domain in the area bounded by the profile of the cross section of the toner particle and the line dividing the area within 0.1 μm inside the profile of the cross section (the area within 0.1 μm from the profile of the cross section) and the sum Wc of the area occupied by the wax domain in the inner area inside the line dividing the area within 0.1 μm inside the profile of the cross section (the inner area within 0.1 μm inside the profile of the cross section) are calculated. Then, the sum Wp of the area occupied by the wax domain in the entire cross section is calculated, and the ratio of Ws to Wp, and the ratio of Ws to Wc are calculated. The arithmetic mean of the cross sections of 20 toner particles is adopted.

[0403] Method for measuring average circularity of toner

[0404] The average circularity of the toner is measured using a flow-type particle image analyzer "FPIA-3000" (manufactured by Sysmex Corporation) under the measurement and analysis conditions during the calibration job.

[0405] The specific measurement method is as follows.

[0406] First, about 20 mL of ion exchange water from which solid impurities and the like were previously removed was poured into a glass container. About 0.2 mL of a dilution obtained by diluting "Contaminon N" (a 10% by mass aqueous solution of a neutral detergent for washing precision measuring instruments at pH 7, which is composed of a nonionic surfactant, anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) with ion exchange water to about three times by mass was added thereto as a dispersant.

[0407] Further, about 0.02 g of the measurement sample was added, and a dispersion treatment was performed for 2 minutes using an ultrasonic disperser to prepare a dispersion liquid for measurement. At this time, cooling was appropriately performed so that the temperature of the dispersion liquid became 10° C. to 40° C. As an ultrasonic disperser, a table-type ultrasonic cleaner disperser "VS-150" (manufactured by VELVO-CLEAR Co.) having an oscillation frequency of 50 kHz and an electrical output of 150 W was used, a predetermined amount of ion exchange water was placed in a water tank, and about 2 mL of Contaminon N was added to the water tank.

[0408] A flow-type particle image analyzer (20-fold magnification, number of openings 0.40) equipped with "LUCPLFLN" was used as an objective lens for measurement, and a particle sheath "PSE-900A" (manufactured by Sysmex Corporation) was used as a sheath liquid. The dispersion prepared according to the aforementioned steps was introduced into the flow-type particle image analyzer, and 2000 magnetic toner particles were measured in the HPF measurement mode and the total count mode. From the results, the average circularity of the toner was calculated.

[0409] Method for measuring secondary ion intensity by time-of-flight secondary ion mass spectrometry (TOF-SIMS)

[0410] Using TOF-SIMS, NanoTOFII manufactured by ULVAC-PHI, Inc. was used for peak intensity measurement.

[0411] The analysis conditions were as follows.

[0412] Sample preparation: attaching toner to indium sheet

[0413] Sample pretreatment: None

[0414] Primary ion: Bismuth trimer ion (Bi3 ++ )

[0415] Accelerating voltage: 30 kV

[0416] Charge Neutralization Mode: On

[0417] Measuring mode: positive, negative

[0418] Grating: 200μm

[0419] Measuring time: 30s

[0420] Repetition frequency: 8.2KHz

[0421] Calculation of secondary ion intensity Ib(t) derived from vinyl resin: According to ULVAC-PHI standard software (WinCadense), the total counts of mass numbers from 84.5 to 85.5 were taken as Ib(t).

[0422] Calculation of secondary ion intensity Iw(t) derived from wax: According to ULVAC-PHI standard software (Win Cadense), the total counts of mass numbers from 282.5 to 283.5 were taken as Iw(t).

[0423] Generally, TOF-SIMS is a surface analysis method, and the data in the depth direction is about 1 nm. Therefore, the secondary ion intensity inside the toner is obtained by sputtering the toner with argon cluster ions and scratching the surface.

[0424] The sputtering conditions were as follows.

[0425] Accelerating voltage: 10 kV

[0426] Current: 13nA

[0427] Grating: 600μm

[0428] Irradiation time: 5s

[0429] For the depth measurement, the relationship between the irradiation time and the depth to be removed was confirmed by sputtering a PMMA film under the same conditions in advance, and it was confirmed that 100 nm could be removed within 300 s.

[0430] The secondary ion intensity at 10 nm from the toner surface is a value of secondary ion mass / secondary ion charge number (m / z) measured when sputtering is performed six times under the above-mentioned conditions.

[0431] Furthermore, the secondary ion intensity at the outermost surface of the toner (ie, t=0) is a value of secondary ion mass / secondary ion charge number (m / z) measured without performing toner sputtering.

[0432] Binder resin (A) and method for specifying structures of monoester compound represented by formula (3), and binder resin (A) Method for measuring the molar ratio of the structure represented by formula (1) and the structure represented by formula (2)

[0433] The structures of the binder resin (A) and the monoester compound represented by the formula (3), and the molar ratio of the structure represented by the formula (1) and the structure represented by the formula (2) in the binder resin (A) were determined by nuclear magnetic resonance spectroscopy ( 1 The molecular weight of the samples was determined by spectral analysis using H-NMR (400 MHz, CDCl3, room temperature (25°C)).

[0434] Measuring device: FT NMR device JNM-EX400 (manufactured by JEOL Ltd.)

[0435] Measuring frequency: 400MHz

[0436] Pulse condition: 5.0μs

[0437] Frequency range: 10,500Hz

[0438] Total times: 64 times

[0439] Solvent: Deuterated solvent that dissolves toner is used appropriately

[0440] How to specify the shell structure

[0441] The same method as in the specification of the structure of the binder resin (A) and the monoester compound represented by the formula (3) is used. 1 H-NMR was used to assign the structure of the shell.

[0442] A total of 10 mg of the toner is immersed in the solvent, allowed to stand for 1 minute, and filtered, and the filtrate is used as a measurement sample.

[0443] Method for measuring the amount of wax

[0444] In the above-mentioned method of measuring the glass transition temperature of the toner, the amount of heat absorption ΔH1 (J / g) derived from the wax is calculated.

[0445] In addition, the heat endotherm of the wax alone was measured under the same conditions to obtain the heat endotherm ΔH2 (J / g).

[0446] The amount of wax (mass %) was calculated from ΔH1 / ΔH2×100.

[0447] Example

[0448] The present disclosure will be specifically described below with reference to Examples, but the present disclosure is not limited to these Examples. Unless otherwise specified, the parts in the Examples are based on mass.

[0449] Production Example of Binder Resin (A) 1

[0450] A diol (10.6 parts) represented by the following formula (21) was added.

[0451]

[0452] A diol represented by the following formula (22) (39.4 parts),

[0453]

[0454] 0.1 parts of hydrogen sulfite were dissolved in 1100 parts of a 5% by mass sodium hydroxide aqueous solution. 500 parts of dichloromethane were added thereto, and then, while stirring and keeping the temperature at 15°C, 60.0 parts of phosgene were blown in over 60 minutes.

[0455] After the blowing of phosgene was completed, 1.0 part of p-tert-butylphenol was added as a molecular weight regulator and stirred to emulsify the reaction liquid. After emulsification, 0.3 parts of triethylamine was added, and the mixture was stirred at 23° C. for 1 hour to polymerize.

[0456] After the polymerization was completed, the reaction solution was separated into an aqueous phase and an organic phase, the organic phase was neutralized with phosphoric acid, and repeatedly washed with water until the conductivity of the washing solution (aqueous phase) was no more than 10 μS / cm. The obtained polymer solution was added dropwise to warm water maintained at 45° C., and the solvent was removed by evaporation to obtain a white powdery precipitate. The obtained precipitate was filtered and dried at 110° C. for 24 hours to obtain a binder resin (A) 1.

[0457] As through 1 As a result of H-NMR confirmation of the obtained binder resin (A) 1, the binder resin (A) 1 included 30 mol % of the structure represented by the formula (1) and 70 mol % of the structure represented by the formula (2).

[0458] Production Examples of Binder Resins (A) 2 to 6

[0459] In addition to changing the type of diol used so that R 11 and R in formula (2) 21 As shown in Table 1, Binder Resins (A) 2 to 6 were produced in the same manner as in the Production Example of Binder Resin (A) 1, except that the molar ratio and amount of the structure represented by Formula (1) and the structure represented by Formula (2) were changed as shown in Table 1.

[0460] Production Example of Photosensitive Member 1

[0461] A total of 3.0 parts of a metal-free phthalocyanine pigment as a charge generating substance,

[0462] 60.0 parts of a compound represented by the following formula (23) as a charge transporting substance,

[0463]

[0464] 12.0 parts of a compound represented by the following formula (24) and 28.0 parts of a compound represented by the following formula (25) as an electron transporting substance,

[0465]

[0466] (Wherein, t-Bu represents tert-butyl.)

[0467]

[0468] 100 parts of a binder resin (A) as a binder resin, and

[0469] 800 parts of tetrahydrofuran as solvent

[0470] Put into container.

[0471] Using a rod-shaped ultrasonic disperser, the material and the solvent in the container were mixed for 2 minutes to disperse the material in the solvent. In addition, the material and the solvent were mixed for 50 hours using a ball mill, and the material was dispersed in the solvent to prepare a photosensitive layer coating liquid.

[0472] The photosensitive layer coating solution was dip-coated on an aluminum support as a conductive substrate and dried at 100° C. for 40 minutes to obtain a photosensitive member 1 having a film thickness of 25 μm and a single-layer photosensitive layer. The single-layer photosensitive layer corresponds to the surface layer of the photosensitive member 1 .

[0473] Production method of photosensitive members 2 to 6

[0474] Photosensitive members 2 to 6 were produced in the same manner as in the production method of photosensitive member 1 except that binder resin (A) 1 was changed as shown in Table 1. Each of photosensitive members 2 to 6 had a single-layer type photosensitive layer, and each single-layer type photosensitive layer corresponded to the surface layer of each photosensitive member.

[0475] [Table 1]

[0476]

[0477] Production method of photosensitive member 7

[0478] A total of 3.0 parts of a metal-free phthalocyanine pigment as a charge generating substance,

[0479] 60.0 parts of a compound represented by formula (23) as a charge transporting substance,

[0480] 12.0 parts of a compound represented by the following formula (24) and 28.0 parts of a compound represented by the following formula (25) as an electron transporting substance,

[0481] 1.0 part of silica particles surface-treated with hexamethyldisilazane (AerosilRX200, manufactured by Nippon Aerosil Co., Ltd.) as an additive,

[0482] 100 parts of a binder resin (A) 2 as a binder resin, and

[0483] 800 parts of tetrahydrofuran as solvent

[0484] Put into container.

[0485] Using a rod-shaped ultrasonic disperser, the material and the solvent in the container were mixed for 2 minutes to disperse the material in the solvent. In addition, the material and the solvent were mixed for 50 hours using a ball mill, and the material was dispersed in the solvent to prepare a photosensitive layer coating liquid.

[0486] The photosensitive layer coating solution was dip-coated on an aluminum support as a conductive substrate and dried at 100° C. for 40 minutes to obtain a photosensitive member 7 having a film thickness of 25 μm and a single-layer photosensitive layer. The single-layer photosensitive layer corresponds to the surface layer of the photosensitive member 7 .

[0487] Production method of wax W1

[0488] A total of 100 parts of behenyl alcohol as an alcohol monomer and 80 parts of stearic acid as a carboxylic acid monomer were added to a reaction vessel equipped with a thermometer, a nitrogen inlet tube, a stirrer, a Dean-Stark water trap and a Dimroth cooling tube, and an esterification reaction was performed at 200° C. for 15 hours.

[0489] A total of 20 parts of toluene and 25 parts of isopropanol were added to the obtained ester compound, 190 parts of a 10% potassium hydroxide aqueous solution in an amount equivalent to 1.5 times the acid value of the ester compound was added, and the mixture was stirred at 70°C for 4 hours. Then, the water tank portion was taken out. After further adding 20 parts of ion exchange water and stirring at 70°C for 1 hour, the water tank portion was taken out and washed. The above washing steps were repeated until the pH of the water tank taken out became neutral.

[0490] Thereafter, the solvent was removed at 200° C. under a reduced pressure of 1 kPa to obtain behenyl stearate (wax W1) which is a monoester compound of behenyl alcohol and stearic acid and is a final target product. Table 1 shows the physical properties of the obtained wax W1.

[0491] Production method of waxes W2 to W6

[0492] Waxes W2 to W6 were obtained in the same manner as in the production method of wax W1, except that the monomers were changed as shown in Table 2. Table 2 shows the physical properties of the obtained waxes W2 to W6.

[0493] [Table 2]

[0494]

[0495] Production method of polyester 1

[0496]

[0497] The above materials were placed in a heated and dried two-necked flask, nitrogen was introduced into the container to maintain an inert atmosphere, and the temperature was raised under stirring. Thereafter, a polycondensation reaction was carried out at 150° C. to 230° C. for about 12 hours, and then the pressure was gradually reduced at 210° C. to 250° C. to obtain polyester 1.

[0498] Polyester 1 had a number average molecular weight (Mn) of 18,200, a weight average molecular weight (Mw) of 74,100, and a glass transition temperature (Tg) of 58.6°C.

[0499] Method for producing toner 1

[0500] -Polymerizable monomer: 74 parts styrene, 26 parts n-butyl acrylate

[0501] - Colorant: Carbon black (manufactured by Mitsubishi Chemical Corp., trade name: #25B) 7 parts

[0502] - Cross-linking agent: divinylbenzene 0.74 parts

[0503] - Charge control agent: styrene / acrylic resin (manufactured by Fujikura Kasei Co., Ltd., trade name: FCA-592P) 0.37 parts

[0504] -Molecular weight regulator: 1 part of tetraethylthiuram disulfide

[0505] - Macromonomer: polymethacrylate macromonomer (manufactured by Toagosei Chemical Industry Co., Ltd., trade name: AA6, Tg = 94° C.) 0.25 parts

[0506] After the above materials were stirred and mixed with a conventional stirring device, the components were uniformly dispersed with a media type disperser and heated to 63°C.

[0507] A total of 20 parts of wax W1 were added thereto, mixed, and dissolved to obtain a polymerizable monomer composition.

[0508] Meanwhile, in a stirring tank, at room temperature, an aqueous solution prepared by dissolving 4.1 parts of sodium hydroxide in 50 parts of ion-exchanged water was gradually added under stirring to an aqueous solution prepared by dissolving 7.4 parts of magnesium chloride in 250 parts of ion-exchanged water to prepare a magnesium hydroxide colloidal dispersion (3.0 parts of magnesium hydroxide).

[0509] At room temperature, the above polymerizable monomer composition was added to the magnesium hydroxide colloidal dispersion obtained as described above, the temperature was raised to 60° C., the mixture was stirred until the droplets became stable, 5 parts of tert-butyl peroxy-2-ethylhexanoate (manufactured by NOF Corp., trade name: Perbutyl O) as a polymerization initiator were added thereto, and an in-line emulsifying disperser (manufactured by Taiheiyo Kiko Co., Ltd., trade name: MILDER) was used to perform high shear stirring at a rotation speed of 15,000 rpm and form droplets of the polymerizable monomer composition.

[0510] A magnesium hydroxide colloidal dispersion in which droplets of a polymerizable monomer composition are dispersed is put into a reactor equipped with a stirring blade, heated to 89°C and controlled to be constant, and a polymerization reaction is performed. Then, when the polymerization conversion rate reaches 98%, the temperature in the system is reduced to 75°C, and after reaching 75°C for 15 minutes, 3 parts of methyl methacrylate as a polymerizable monomer for the shell and 0.36 parts of 2,2'-azobis[2-methyl-N-(1,1-bis(hydroxymethyl)2-hydroxyethyl)propionamide]tetrahydrate (manufactured by Wako Pure Chemical Industries, Ltd., trade name: VA086) are added. After further polymerization for 3 hours, the reaction is stopped to obtain an aqueous dispersion of colored resin particles having a pH of 9.5.

[0511] Thereafter, the aqueous dispersion of the colored resin particles was heated to 80°C and 3 / (hr·kg) of nitrogen flow rate for 5 hours, and then cooled to 25°C. Next, while stirring the resulting aqueous dispersion at 25°C, the pH of the system was set to not more than 6.5 with sulfuric acid, acid washing was performed, water was separated by filtration, and then 500 parts of ion exchange water was newly added to perform re-slurrying and washing with water. Thereafter, dehydration and water washing were repeated several times to separate the solid content by filtration, and then the solid content was put into a dryer and dried at a temperature of 40°C for 12 hours, thereby obtaining toner particles 1.

[0512] To the toner particles 1 (100 parts) obtained as described above, 0.7 parts of hydrophobized silica fine particles having a number average primary particle size of 7 nm and 1 part of hydrophobized silica fine particles having a number average primary particle size of 50 nm were added and mixed using a high-speed stirrer (trade name: FM mixer, manufactured by Nippon Coke Industry Co., Ltd.) to produce Toner 1. Table 4 shows the physical properties of Toner 1 thus obtained.

[0513] Method for producing toner 2

[0514] -Polymerizable monomer: 74 parts styrene, 26 parts n-butyl acrylate

[0515] -Colorant: Carbon black (Mitsubishi Chemical Corp., trade name: #25B) 7 parts

[0516] - Cross-linking agent: divinylbenzene 0.74 parts

[0517] - Charge control agent: styrene / acrylic resin (manufactured by Fujikura Kasei Co. Ltd., trade name: FCA-592P) 0.50 parts

[0518] -Molecular weight regulator: 1 part of tetraethylthiuram disulfide

[0519] - Macromonomer: polymethacrylate macromonomer (manufactured by Toagosei Chemical Industry Co., Ltd., trade name: AA6, Tg = 94° C.) 0.17 parts

[0520] After the above materials were stirred and mixed with a conventional stirring device, the components were uniformly dispersed with a media type disperser and heated to 63°C.

[0521] A total of 20 parts of wax W1 were added thereto, mixed, and dissolved to obtain a polymerizable monomer composition.

[0522] Meanwhile, in a stirring tank, at room temperature, an aqueous solution prepared by dissolving 4.1 parts of sodium hydroxide in 50 parts of ion-exchanged water was gradually added under stirring to an aqueous solution prepared by dissolving 7.4 parts of magnesium chloride in 250 parts of ion-exchanged water to prepare a magnesium hydroxide colloidal dispersion (3.0 parts of magnesium hydroxide).

[0523] At room temperature, the above polymerizable monomer composition was added to the magnesium hydroxide colloidal dispersion obtained as described above, the temperature was raised to 60° C., the mixture was stirred until the droplets became stable, 5 parts of tert-butyl peroxy-2-ethylhexanoate (manufactured by NOF Corp., trade name: Perbutyl O) as a polymerization initiator were added thereto, and an in-line emulsifying disperser (manufactured by Taiheiyo Kiko Co., Ltd., trade name: MILDER) was used to perform high shear stirring at a rotation speed of 15,000 rpm and form droplets of the polymerizable monomer composition.

[0524] A magnesium hydroxide colloidal dispersion in which droplets of a polymerizable monomer composition are dispersed is put into a reactor equipped with a stirring blade, heated to 89°C and controlled to be constant, and a polymerization reaction is performed. Then, when the polymerization conversion rate reaches 98%, the temperature in the system is reduced to 75°C, and after reaching 75°C for 15 minutes, 2 parts of methyl methacrylate as a polymerizable monomer for the shell and 0.36 parts of 2,2'-azobis[2-methyl-N-(1,1-bis(hydroxymethyl)2-hydroxyethyl)propionamide]tetrahydrate (manufactured by Wako Pure Chemical Industries, Ltd., trade name: VA086) dissolved in 10 parts of ion exchange water are added. After further polymerization for 3 hours, the reaction is stopped to obtain an aqueous dispersion of colored resin particles having a pH of 9.5.

[0525] Thereafter, the aqueous dispersion of the colored resin particles was heated to 80°C and 3 / (hr·kg) of nitrogen flow rate for 5 hours, and then cooled to 25°C. Next, while stirring the resulting aqueous dispersion at 25°C, the pH of the system was set to not more than 6.5 with sulfuric acid, acid washing was performed, water was separated by filtration, and then 500 parts of ion exchange water was newly added to perform re-slurrying and washing with water. Thereafter, dehydration and water washing were repeated several times to separate solid components by filtration, and then the solid components were put into a dryer and dried at a temperature of 40°C for 12 hours to obtain toner particles 2.

[0526] To the toner particles 2 (100 parts) obtained as described above, 0.7 parts of hydrophobized silica fine particles having a number average primary particle size of 7 nm and 1 part of hydrophobized silica fine particles having a number average primary particle size of 50 nm were added and mixed using a high-speed stirrer (trade name: FM mixer, manufactured by Nippon Coke Industry Co., Ltd.) to produce toner 2. Table 4 shows the physical properties of the toner 2 thus obtained.

[0527] Production methods of toners 3 to 10, 12 and 13

[0528] Toners 3 to 10, 12, and 13 were produced in the same manner as in the production method of Toner 1, except that the kind and amount of the wax used were changed as shown in Table 3. Table 4 shows the physical properties of Toners 3 to 10, 12, and 13.

[0529] Method for producing toner 11

[0530] The following materials were mixed with an FM mixer ("FM-20" manufactured by Nippon Coke Industry Co., Ltd.) at a rotation speed of 2000 rpm for 4 minutes.

[0531] -Polyester 1 90 parts

[0532] - Charge control agent ("FAC-207P", manufactured by Fujikura Kasei Co., Ltd.) 3 parts

[0533] -Carbon black (Mitsubishi Chemical Corp., trade name: #25B) 4 parts

[0534] - Wax W1 3 parts

[0535] The obtained mixture was melt-kneaded by a twin-screw extruder ("PCM-30" manufactured by Ikegai Co., Ltd.) under the conditions of a melt-kneading temperature (barrel temperature) of 120° C., a rotation speed of 150 rpm, and a processing speed of 100 g / min. The obtained melt-kneaded product was coarsely pulverized to about 2 mm by a Rotoplex pulverizer (manufactured by Alpine AG), and pulverized by a mechanical pulverizer ("Turbomill T250" manufactured by Freund Turbo Co., Ltd.). The obtained pulverized product was classified by an air classifier ("EJ-L3 type" manufactured by Nittetsu Mining Co., Ltd.) to obtain toner particles 11 having an average particle size of 8.5 μm.

[0536] A total of 100 parts of the obtained toner particles 11, 0.8 parts of silica fine particles ("RA200" manufactured by Nippon Aerosil Co., Ltd.), and 0.8 parts of titanium oxide ("EC100" manufactured by Titanium Industry Co., Ltd.) were mixed with an FM mixer ("FM-20" manufactured by Nippon Coke Industry Co., Ltd.) at a rotation speed of 2000 rpm for 5 minutes to obtain Toner 11.

[0537] Table 4 shows the physical properties of Toner 11.

[0538] [Table 3]

[0539]

[0540] [Table 4]

[0541]

[0542] [Table 5]

[0543]

[0544] Example 1

[0545] The following evaluation was performed using the combination of Toner 1 and Photosensitive Member 1 .

[0546] Table 6 shows the evaluation results.

[0547] [Table 6]

[0548]

[0549] Evaluation 1: Evaluation of image clarity

[0550] Image clarity was evaluated by using HL-5470DW (monochrome laser printer, manufactured by Brother Industries, Ltd.), and a box from which the paper dust collecting roller was taken out. The evaluation was performed after printing out 5,000 sheets of a continuous horizontal line pattern with a line width of 2 mm and an interval of 5 mm in a high temperature and high humidity environment (temperature 35.0°C, relative humidity 85%). The paper used was OCE RED LABEL (basis weight: 80 g / m 2 ).

[0551] Image clarity is an index indicating whether the lines of the toner carried on the electrophotographic photosensitive member are broken when printing thin lines, so that the boundary of the printed part becomes rough or the lines appear blurred. Image clarity was evaluated by printing a continuous horizontal line pattern with a line width of 2 mm and an interval of 5 mm, confirming the image with an optical microscope, and evaluating according to the following criteria.

[0552] A: Lines are formed with a constant width without interruption.

[0553] B: The width of the line is partially disrupted, but there is no interruption.

[0554] C: The width of the line is completely disrupted, but the line is not interrupted.

[0555] D: Part of the line is broken.

[0556] Evaluation 2: Evaluation of image defects originating from photosensitive members

[0557] Image defects (blank spots) originating from the photosensitive member were evaluated by using HL-5470DW (monochrome laser printer, manufactured by Brother Industries, Ltd.), and a box from which the paper dust collection roller was taken out. The evaluation was performed after printing out 5000 sheets of a continuous horizontal line pattern having a line width of 2 mm and an interval of 5 mm in a high temperature and high humidity environment (temperature 35.0° C., relative humidity 85%). The paper used was OCE RED LABEL (basis weight: 80 g / m 2 ).

[0558] After printing the above 5,000 sheets, a solid image was printed and evaluated according to the following criteria.

[0559] A: There are no image defects.

[0560] B: There is a portion with low density at the photosensitive member interval.

[0561] C: There are blank spots at the photosensitive member interval.

[0562] D: Vertical streaks are present.

[0563] Evaluation 3: Evaluation of low temperature fixability

[0564] The low temperature fixability was evaluated in a normal temperature and humidity environment (temperature 25.0° C., relative humidity 60%) by using HL-5470DW (monochrome laser printer, manufactured by Brother Industries, Ltd.), and a cartridge (from which a paper dust collecting roller was taken out). The printer was modified so that the fixing temperature of the fixing device in the image forming apparatus could be arbitrarily set.

[0565] Using this device, the fixing temperature of the fixing device was adjusted in the range of 180°C to 230°C at intervals of 5°C, and FOX RIVER BOND paper (110 g / m 2 ), and a solid black image was output at a printing rate of 100%. At this time, whether or not there were blank spots in the image of the solid image portion was visually evaluated, and the lowest temperature at which the blank spots were generated was evaluated as low-temperature fixability.

[0566] A: Blank spots appear at temperatures below 200°C.

[0567] B: A blank spot appears at a temperature of 200°C or higher and lower than 210°C.

[0568] C: A blank spot appears at 210°C or higher and lower than 220°C.

[0569] D: Blank spots appear above 220°C.

[0570] Evaluation 4: Evaluation of storage stability

[0571] The storage stability was evaluated by the following procedure.

[0572] HL-5470DW (monochrome laser printer, manufactured by Brother Industries, Ltd.), and a box (from which a paper dust collecting roller was taken out) were used to print out a solid image in a normal temperature and humidity environment (temperature 25.0° C., relative humidity 60%), and then stored for 40 days in a severe environment (temperature 40.0° C., relative humidity 95%). After storage, a solid image was output in a normal temperature and humidity environment (temperature 25.0° C., relative humidity 60%), and the image densities before and after storage were compared and evaluated. The density of the solid image was measured with a Macbeth reflection densitometer (manufactured by Macbeth Co.).

[0573] A: The concentration difference is less than 0.05.

[0574] B: The density difference is at least 0.05 and less than 0.10.

[0575] C: The density difference is at least 0.10 and less than 0.20.

[0576] D: The density difference is at least 0.20.

[0577] Examples 2 to 16, Comparative Examples 1 to 5

[0578] In Examples 2 to 16 and Comparative Examples 1 to 5, evaluation was performed in the same manner as in Example 1, except that the toner and photosensitive member combinations were changed as shown in Table 5. Table 6 shows the evaluation results.

[0579] While the present invention has been described with reference to exemplary embodiments, it is to be understood that the invention is not limited to the disclosed exemplary embodiments.The scope of the following claims is to be accorded the broadest interpretation so as to encompass all such modifications and equivalent structures and functions.

Claims

1. An image forming device, comprising: Electrophotographic photosensitive member; and A developing device for supplying a toner onto the electrophotographic photosensitive member, the developing device having the toner, characterized in that: The electrophotographic photosensitive member has a surface layer containing a binder resin A, The toner has toner particles, The toner particles have a core-shell structure having: a core comprising a binder resin B and a wax; and a shell layer formed on the surface of the core, The binder resin A has: A structure represented by the following formula (1); and The structure represented by the following formula (2): The value of the molar ratio of the structure represented by the formula (1) to the structure represented by the formula (2) in the binder resin A, i.e., (the structure represented by the formula (1)) / (the structure represented by the formula (2)) is 25 / 75 to 70 / 30: Among them, R 11 and R 21 Each independently represents a hydrogen atom or a methyl group, R 22 and R 23 Each independently represents a hydrogen atom, a methyl group, an ethyl group or a phenyl group, or R 22 and R 23 are connected to each other to form a cycloalkylidene group, The wax comprises a monoester compound represented by the following formula (3): R 31 -COO-R 32 (3) Among them, R 31 and R 32 each independently represents an alkyl group having 10 to 30 carbon atoms, The toner contains the wax in an amount of 7.0 to 14.7% by mass, and The toner has an average circularity of at least 0.

970.

2. The image forming apparatus according to claim 1, wherein In the cross section of the toner observed using a transmission electron microscope, the wax is observed as domains. The sum of the areas occupied by the domains in the entire cross section is defined as Wp, The sum of the areas occupied by the domains in the region bounded by the outline of the cross section and the line dividing the region 0.1 μm inside the outline of the cross section is defined as Ws, and When the sum of the areas occupied by the domains in the inner region inside the line dividing the region 0.1 μm inside the outline of the cross section is defined as Wc, The ratio of said Ws to said Wp is 0.0 to 10.0%, and The ratio of the Ws to the Wc is 0.00 to 0.50%.

3. The image forming apparatus according to claim 1 or 2, wherein when the dispersion term and the polarity term of the Hansen solubility parameter in the binder resin B are defined as SD1 (J / cm 3 ) 1 / 2 and SP1(J / cm 3 ) 1 / 2 , and the dispersion term and polar term of the Hansen solubility parameter in the wax are defined as SD2 (J / cm 3 ) 1 / 2 and SP2(J / cm 3 ) 1 / 2 When , the following equations (4) and (5) are satisfied: 0.00≤SD1-SD2≤3.00 (4) 0.00≤SP1-SP2≤0.30 (5).

4. The image forming apparatus according to claim 1 or 2, wherein when the dispersion term and the polarity term of the Hansen solubility parameter in the wax are SD2 (J / cm 3 ) 1 / 2 and SP2(J / cm 3 ) 1 / 2 , and the dispersion term and polar term of the Hansen solubility parameter in the structure shown in formula (2) are SD(A2)(J / cm 3 ) 1 / 2 and SP(A2)(J / cm 3 ) 1 / 2 When , the following equations (6) and (7) are satisfied: 2.50≤SD(A2)-SD2≤5.00 (6) 2.50≤SP(A2)-SP2≤6.00 (7).

5. The image forming apparatus according to claim 1 or 2, wherein when the dispersion term and the polarity term of the Hansen solubility parameter in the wax are SD2 (J / cm 3 ) 1 / 2 and SP2(J / cm 3 ) 1 / 2 , and the dispersion term and polar term of the Hansen solubility parameter in the structure shown in formula (1) are SD(A1)(J / cm 3 ) 1 / 2 and SP(A1)(J / cm 3 ) 1 / 2 When , the following equations (8) and (9) are satisfied: 2.50≤SD(A1)-SD2≤5.00 (8) 2.50≤SP(A1)-SP2≤6.00 (9). 6 . The image forming apparatus according to claim 1 , wherein the shell layer of the toner particle comprises a vinyl resin including a monomer unit derived from methyl methacrylate.

7. The image forming apparatus according to claim 6, wherein In secondary ion depth distribution measurement of the surface of the toner by time-of-flight secondary ion mass spectrometry, When the secondary ion intensities derived from the wax and the vinyl resin at a depth of t nm from the surface of the toner are defined as Iw(t) and Ib(t), respectively, the following formulas (10) and (11) are satisfied in the range of 0≤t≤10: Iw(t) <Ib(t) (10) Iw(t)<0.005 (11).

8. A process cartridge detachably mounted to a main body of an image forming apparatus, The processing box comprises: Electrophotographic photosensitive member; and A developing device for supplying a toner onto the electrophotographic photosensitive member, the developing device having the toner, characterized in that: The electrophotographic photosensitive member has a surface layer containing a binder resin A, The toner has toner particles; The toner particles have a core-shell structure having: a core comprising a binder resin B and a wax; and a shell layer formed on the surface of the core, The binder resin A has: A structure represented by the following formula (1); and The structure represented by the following formula (2): The value of the molar ratio of the structure represented by the formula (1) to the structure represented by the formula (2) in the binder resin A, i.e., (the structure represented by the formula (1)) / (the structure represented by the formula (2)) is 25 / 75 to 70 / 30: Among them, R 11 and R 21 Each independently represents a hydrogen atom or a methyl group, R 22 and R 23 Each independently represents a hydrogen atom, a methyl group, an ethyl group or a phenyl group, or R 22 and R 23 are connected to each other to form a cycloalkylidene group, and The wax comprises a monoester compound represented by the following formula (3): R 31 -COO-R 32 (3) Among them, R 31 and R 32 each independently represents an alkyl group having 10 to 30 carbon atoms, The toner contains the wax in an amount of 7.0 to 14.7% by mass, and The toner has an average circularity of at least 0.970.